Polymer-coated lipid nanoparticles and preparation method and pharmaceutical preparation thereof

By using polymer-encapsulated lipid nanoparticles technology, the problem of instability of RNA vaccines and therapeutic agents under non-cold chain conditions is solved, and RNA stability and transfection efficiency are achieved over a wide temperature range.

CN116004728BActive Publication Date: 2025-02-28SHENZHEN UNIV GENERAL HOSPITAL +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111225943.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-21
Publication Date
2025-02-28
Estimated Expiration
2041-10-21

AI Technical Summary

Technical Problem

Existing RNA vaccines and therapeutic agents are unstable in an in vitro exposed environment and require cold chain storage and transportation, resulting in huge challenges in supply, distribution and dispatch.

Method used

Using polymer-encapsulated lipid nanoparticles, a vesicle structure is formed through the combination of amphiphilic block copolymer and cationic lipids to encapsulate RNA, improving the stability of RNA and the adaptability of storage conditions.

Benefits of technology

Long-term stable storage of RNA at 2-8°C or even room temperature and transportation under non-cold chain conditions, improving the biological activity and transfection efficiency of RNA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116004728B_ABST
    Figure CN116004728B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of bioengineering technology, and specifically relates to a polymer-coated lipid nanoparticle, a preparation method thereof, and a pharmaceutical preparation. The polymer-coated lipid nanoparticles provided by the present invention include polymer vesicles and lipids encapsulated in the polymer vesicles; the polymer constituting the polymer vesicles is an amphiphilic block copolymer; the amphiphilic block copolymer contains a hydrophilic polymer block and a hydrophobic polymer block, and the hydrophilic polymer block accounts for 20 to 50 wt% of the amphiphilic block polymer; the lipids include lipids. The present invention enables the polymer to form a vesicle structure by limiting the mass ratio of the hydrophilic polymer block and the hydrophobic polymer block in the amphiphilic block copolymer, while encapsulating the lipids in the vesicles; the polymer-coated lipid nanoparticles provided by the present invention can improve the stability of the load (such as saRNA, mRNA or DNA), which is beneficial to its long-term storage at 2 to 8°C or even at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bioengineering, and specifically relates to a polymer-wrapped lipid nanoparticle and a preparation method and a pharmaceutical preparation thereof. Background Art

[0002] Biomacromolecules such as RNA (e.g., mRNA (messenger RNA), self-amplifying RNA (saRNA) (self-replicating RNA) and siRNA (small interfering RNA)) and DNA (e.g., plasmids) have a variety of applications, including vaccines and gene therapy. For example, mRNA and saRNA have been tested in preclinical and clinical trials for a variety of vaccine indications, such as influenza, rabies, HIV, Zika virus, Ebola virus, and tumor vaccines. Examples of RNA vaccines for COVID-19 include the currently marketed Moderna mRNA-1273, Pfizer and BioNTech mRNA vaccine BNT162b2, and Imperial College London's (saRNA) vaccine. mRNA is usually the part of the antigen that can be translated effectively, while saRNA not only contains the information of the target antigen protein, but also enables RNA to self-replicate in the cell. Therefore, saRNA can produce a large amount of target protein at a very low dosage (one tenth or one hundredth of the mRNA dosage).

[0003] Although mRNA and saRMA have broad application prospects in vaccines and other treatments, their commercial application still faces huge challenges. RNA molecules are very unstable and easily degraded in an environment exposed in vitro, so RNA needs to be stored in an extremely low environment. Any interruption or destruction of the "cold chain" will significantly reduce the biological activity of RNA. For example, Pfizer and BioNTech's mRNA vaccine BNT162b2 needs to be stored at -70°C, and the shelf life can be extended by up to 6 months. Pfizer's vaccine transport ship is refilled with dry ice every 5 days and can be stored for up to 30 days. After arriving at the hospital, the vaccine containing saRNA can be stored for 5 days under refrigerated conditions of 2 to 8°C. Moderna's mRNA vaccine needs to be stored at -20°C. Therefore, the development of a stable nucleic acid delivery system at 2 to 8°C and under non-cold chain conditions for vaccines or other treatments is crucial and highly challenging for its overall supply, distribution and scheduling.

[0004] In the past few decades, advances in bioengineering and nanotechnology have produced many delivery technologies. As the most widely studied mRNA delivery system, liposomes need to be positively charged to electrostatically capture mRNA, and need to have a certain positive charge density to ensure that they can break through the lysosomal barrier. However, the cargo in liposomes is prone to leakage because the lipid membrane is easily destroyed when interacting with the negatively charged cell membrane. In addition, the surface charge of liposomes affects their aggregation behavior and affects the adsorption of serum proteins after in vivo injection. The charge on the surface of liposomes will lead to rapid clearance of mRNA and reduce the transfection efficiency in vivo.

[0005] Polymer vesicles have also been studied for the delivery of oligonucleotides, however, the synthesis of cationic polymers requires a rather complex process due to their complex biological requirements. In addition, due to the greater molecular weight and instability of mRNA and saRNA relative to oligonucleotides, efficient saRNA delivery is more difficult. Although there have been some polymer vesicle delivery systems that can successfully deliver mRNA or saRNA, they all need to be freshly prepared or stored at -80°C for subsequent use. Summary of the invention

[0006] In view of this, the present invention provides a polymer-coated lipid nanoparticle and a preparation method and a pharmaceutical preparation thereof. The polymer-coated lipid nanoparticle provided by the present invention can enable nucleic acid loads (especially RNA) to maintain long-term stability at a temperature of 2 to 8°C, and can be transported under non-cold chain storage conditions.

[0007] In order to solve the above technical problems, the present invention provides a polymer-coated lipid nanoparticle, including a polymer vesicle and a lipid encapsulated in the polymer vesicle; the polymer constituting the polymer vesicle is an amphiphilic block copolymer; the amphiphilic block copolymer contains a hydrophilic polymer block and a hydrophobic polymer block, and the mass percentage of the hydrophilic polymer block is 20-50%; the lipid includes a cationic lipid.

[0008] Preferably, the hydrophilic polymer block comprises one or more of polyether, polyamino acid, poly(2-methyloxazoline), poly(2-methyloxazoline), polyamide, polyenol, polyalkenoic acid, polyphosphate, polyether derivative, polyamino acid derivative, poly(2-methyloxazoline) derivative, poly(2-methyloxazoline) derivative, polyamide derivative, polyenol derivative, polyalkenoic acid derivative and polyphosphate derivative;

[0009] The hydrophobic polymer block includes one or more of polyester, polycarbonate, polyethylene, polybutadiene, polylactic acid, polylactic acid-polyglycolic acid, polydimethylsiloxane, polymethyl methacrylate, polystyrene, polyester derivatives, polycarbonate derivatives, polyethylene derivatives, polybutadiene derivatives, polylactic acid derivatives, polylactic acid-polyglycolic acid derivatives, polydimethylsiloxane derivatives, polymethyl methacrylate derivatives and polystyrene derivatives.

[0010] Preferably, the weight average molecular weight of the amphiphilic block copolymer is 4 to 100 KDa;

[0011] The weight average molecular weight of the hydrophilic polymer block in the amphiphilic block copolymer is 2 to 20 KDa.

[0012] Preferably, the cationic lipids include (2,3-dioleoyl-propyl)-trimethylammonium chloride, dioleoylpropyl trimethylammonium chloride, ethyl phosphatidylcholine, 3β-[N-(N',N'-dimethylaminoethane)-carbamoyl] cholesterol, N4-cholesterol-spermidine, 1,2-dioloxy-3-dimethylaminopropane, trimethyl-2,3-oleoyloxypropylammonium bromide, dimethyl-2,3-dioleyloxypropyl-2-(2-sperminecarboxamido)ethylammonium trifluoroacetate, trimethyldodecylammonium bromide, trimethyltetradecylammonium bromide, trimethylhexadecylammonium bromide, di ... One or more of methyl dioctadecyl ammonium bromide, dimethyl-2-hydroxyethyl-2,3-dioleyloxy ammonium bromide, dimethyl-2-hydroxyethyl-2,3-dioleyloxy ammonium bromide, dimethyl-3-hydroxypropyl-2,3-dioleyloxy ammonium bromide, dimethyl-4-hydroxybutyl-2,3-dioleyloxy ammonium bromide, dimethyl-4-hydroxypentyl-2,3-dioleyloxy ammonium bromide, dimethyl-2-hydroxyethyl-2,3-dihexadecyloxy propyl ammonium bromide, dimethyl-2-hydroxyethyl-2,3-dioctadecyloxy propyl ammonium bromide and D-Lin-MC3-DMA;

[0013] The lipids also include auxiliary lipids, and the auxiliary lipids include phosphatidylethanolamine, dioleoylphosphatidylcholine, phosphatidylcholine, cholesterol, and dioleoylphosphatidylethanolamine.

[0014] Preferably, the molar ratio of the amphiphilic block copolymer to the lipid is 0.01 to 1:1.

[0015] Preferably, the invention further comprises a stabilizer, which is encapsulated inside the polymer-encapsulated lipid nanoparticles and / or located outside the polymer-encapsulated lipid nanoparticles.

[0016] Preferably, the stabilizer comprises one or more of carbohydrates, polyols, surfactants, pharmaceutically acceptable complexes and pharmaceutically acceptable salts.

[0017] Preferably, the polymer-encapsulated lipid nanoparticles further comprise a targeting ligand.

[0018] The present invention provides a method for preparing polymer-encapsulated lipid nanoparticles according to the above technical solution, comprising the following steps:

[0019] Dissolving the amphiphilic block copolymer and lipid in an organic solvent to obtain an organic phase; the mass percentage of the hydrophilic polymer block in the amphiphilic block copolymer is 20-50%; the lipid includes a cationic lipid;

[0020] The organic phase is mixed with water for self-assembly coating, and the organic solvent is removed to obtain the polymer-coated lipid nanoparticles.

[0021] The present invention provides a pharmaceutical preparation, comprising polymer-coated lipid nanoparticles and a load; the polymer-coated lipid nanoparticles are the polymer-coated lipid nanoparticles described in the above technical solution or the polymer-coated lipid nanoparticles prepared by the preparation method described in the above technical solution; the load comprises nucleic acid.

[0022] Preferably, the mass ratio of the amphiphilic block copolymer to the load in the polymer-encapsulated lipid nanoparticles is 5 to 1000:1;

[0023] The loading substances also include peptides, proteins, antibodies, monosaccharides, disaccharides, polysaccharides, small molecule hydrophobic drugs or small molecule hydrophilic drugs.

[0024] The present invention provides a polymer-encapsulated lipid nanoparticle (abbreviated as PE-LNP), including a polymer vesicle and a lipid encapsulated in the polymer vesicle; the polymer constituting the polymer vesicle is an amphiphilic block copolymer; the amphiphilic block copolymer contains a hydrophilic polymer block and a hydrophobic polymer block, and the mass percentage of the hydrophilic polymer block is 20-50%; the lipid includes a cationic lipid. The present invention enables the polymer to form a vesicle structure by limiting the mass ratio of the hydrophilic polymer block and the hydrophobic block polymer in the amphiphilic block copolymer, and at the same time, the lipid is encapsulated in the vesicle; in the present invention, the polymer shell with a vesicle structure has a high mechanical strength that can reduce the leakage of the load, thereby improving the stability of the load (especially nucleic acid RNA), which is beneficial to its long-term storage at 2-8°C or even room temperature, and can be transported under non-cold chain conditions.

[0025] The present invention provides a method for preparing the polymer-encapsulated lipid nanoparticles described in the above technical solution. The preparation method provided by the present invention has simple operation, mild preparation conditions, low production cost, and is suitable for industrial production.

[0026] The present invention also provides a pharmaceutical preparation, comprising polymer-coated lipid nanoparticles and a load; the polymer-coated lipid nanoparticles are the polymer-coated lipid nanoparticles described in the above technical solution or the polymer-coated lipid nanoparticles prepared by the preparation method described in the above technical solution; the load includes nucleic acid. The polymer-coated lipid nanoparticles in the pharmaceutical preparation provided by the present invention have high mechanical strength and can reduce the leakage of the load, thereby improving the stability of the load (especially nucleic acid RNA), which is beneficial to its transportation and long-term storage at 2 to 8°C or even room temperature and non-cold chain conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the preparation process of polymer-encapsulated lipid nanoplasmids (PE-LNPs) loaded with RNA (A) and the intracellular delivery of saRNA mediated by PE-LNP (B);

[0028] Figure 2 PEG prepared in Example 20 5K -PCL 10K Polymer NMR spectra ( 1 H-NMR);

[0029] Figure 3 is the particle size distribution of PE-LNPs prepared in Example 23;

[0030] Figure 4 The SEM images and Cryo-TEM images of the PE-LNP prepared in Examples 1 to 2 and Examples 4 to 5;

[0031] Figure 5 Schematic diagram of the structure of a homogeneous polymer / lipid hybrid membrane (A) and the structural verification process diagram of the PE-LNP provided by the present invention (B-D);

[0032] Figure 6 Schematic diagram (A) and verification diagrams (B-C) of the internal structure of the PE-LNP 11'-65' core without saRNA encapsulation prepared by the present invention;

[0033] Figure 7 A comparison diagram of the effects of polymer molecular weight, N / P molar ratio and polymer / nucleic acid mass ratio on transfection efficiency in the nucleic acid-loaded PE-LNP provided by the present invention;

[0034] Figure 8It is a comparison chart of the in vitro transfection efficiency of PE-LNP with saRNA encapsulated inside and PE-LNP with saRNA adsorbed on the surface, as well as the transfection efficiency after storage for a period of time under different conditions;

[0035] Fig. 9 A in the middle is a fluorescence microscopy comparison of Jurkat cells transfected with mRNA encoding green fluorescent protein (GFP) by different PE-LNPs; Fig. 9 Middle B is a bar graph showing the percentage of Jurkat cells expressing GFP in cells transfected with different PE-LNPs; Fig. 9 Middle C is a comparative bar graph of the mean fluorescence intensity after transfection; Fig. 9 Middle D is a comparative bar graph of cell survival rates after transfection;

[0036] Fig.10 Middle A is a confocal microscopy image showing the intracellular distribution of FITC-loaded PE-LNP 18-80 in HEK293 cells at 4 or 37°C for 4 h; Fig.10 B is Fig.10 The fluorescence intensity of FITC and Lysotracker corresponding to the cross section indicated by the horizontal line in A; Fig.10 Middle C is a confocal microscopy image showing the intracellular distribution of FITC-loaded PE-LNP 18-80 in HEK293 cells in the presence of the endocytosis inhibitor MβCD; Fig.10 Middle D is the endocytosis of PE-LNP 18-80 by HEK293 cells in the presence of various endocytosis inhibitors detected by flow cytometry;

[0037] Fig.11 A in the middle shows the hemolysis after incubation with various PE-LNPs at 37°C for 1 h; Fig.11 Middle B shows the survival rate of HEK293 cells treated with various PE-LNPs for 24 h;

[0038] Fig.12 The figure is a comparison of the protein expression efficiency of different PE-LNPs in mice, the antibody content in mice after immunization, and the weight change after virus stimulation after immunization;

[0039] Fig.13 This is a bar graph comparing the transfection efficiency of HEK293 cells after different PE-LNP liquid states were stored at 4°C for different time periods;

[0040] Fig.14 Schematic diagram of the structure of freeze-dried saRNA and trehalose co-loaded PE-LNP 11-65 (trehalose both inside and outside) and its preparation flow chart;

[0041] Fig.15A in the middle is a comparison of the transfection efficiency of lyophilized saRNA-loaded PE-LNP 11-65 (with different saRNA concentrations before lyophilization and only trehalose on the outside) after reconstitution, where the NC group represents the freshly prepared PE-LNP 11-65 (no trehalose) negative control, (*) and (***) indicate p<0.05 and p<0.001, respectively; Fig.15 B is PE-LNP 11-65 (40 μg mL -1 saRNA) was mixed with different concentrations of trehalose and then lyophilized and reconstituted into HEK293 cells for transfection efficiency. Freshly prepared PE-LNP 11-65 (without trehalose) was used as a negative control;

[0042] Fig.16 For PE-LNP 11-65 (40 μg mL -1 saRNA) external trehalose concentration was 250 mg mL -1 In the case of , lyophilized and stored at 4 °C for 28 days, after reconstitution with RNase-free water, the transfection efficiency of HEK293 cells was evaluated, and freshly prepared PE-LNP 11-65 (without trehalose) was used as a negative control;

[0043] Fig.17 The total trehalose (inside and outside PE-LNP 11-65) concentration was 250 mg mL -1 Effect of trehalose / saRNA mass ratio on in vitro transfection efficiency of freeze-dried samples during PE-LNP preparation under the same conditions, with freshly prepared PE-LNP 11-65 (without trehalose) as negative control, (***) and (****) indicate p<0.001 and p<0.0001, respectively;

[0044] Fig.18 The figure is a comparison of the transfection efficiency of freeze-dried PE-LNP 11-65 with trehalose only on the outside and trehalose both inside and outside after being reconstituted at 40°C for different time periods, where NC is the negative control group, (*), (**), (***) and (****) indicate p<0.05, p<0.01, p<0.001 and p<0.0001, respectively;

[0045] Fig.19 is the transfection efficiency of the lyophilized preparation containing trehalose both on the outside and inside of PE-LNP 11-65 after being stored at 40°C for 14 days and reconstituted, wherein NC is the negative control of freshly prepared PE-LNP without trehalose, and ns indicates no significant difference between the two groups;

[0046] Fig. 20The transfection efficiency of the freeze-dried preparations containing trehalose both on the outside and inside of PE-LNP after being stored at 40°C for different time periods and then reconstituted and then the external trehalose was removed. Among them, PE-LNP 11-65 containing only external trehalose and freshly prepared NC without trehalose were used as the control group; (*), (**), (***) and (****) indicate p<0.05, p<0.01, p<0.001 and p<0.0001, respectively;

[0047] Fig.21 Middle A is a confocal microscopy image of HEK293 cells treated with freshly prepared saRNA and calcein co-encapsulated PE-LNP 11-65 and saRNA, trehalose, and calcein co-encapsulated PE-LNP 11-65 4 hours after treatment; Fig.21 Middle B is the quantitative analysis of the mean fluorescence intensity of calcein in confocal microscopy images analyzed by ImageJ, **** indicates p < 0.0001;

[0048] Fig. 22 A in the middle is the ratio of PE-LNP 11-65 co-encapsulated with mRNA encoding GFP and trehalose and PE-LNP 11-65 loaded with mRNA alone expressing GFP green fluorescence after being treated with HEK293 cells; Fig. 22 B in the figure is the mean fluorescence intensity (MFI) of GFP expression in cells; * and ** indicate p<0.05 and p<0.01, respectively. DETAILED DESCRIPTION

[0049] The invention provides a polymer-wrapped lipid nanoparticle, comprising a polymer vesicle and a lipid encapsulated in the polymer vesicle; the polymer constituting the polymer vesicle is an amphiphilic block copolymer; the amphiphilic block copolymer contains a hydrophilic polymer block and a hydrophobic polymer block, and the mass percentage of the hydrophilic polymer block is 20-50%; the lipid comprises a cationic lipid.

[0050] In the present invention, the polymer-encapsulated lipid nanoparticles include polymer vesicles, and the polymer constituting the polymer vesicles is an amphiphilic block copolymer. In the present invention, the amphiphilic block copolymer includes a hydrophilic polymer block and a hydrophobic polymer block. In the present invention, the hydrophilic polymer block preferably includes one or more of polyether, polyamino acid, poly(2-methyloxazoline) (PMOXA), poly(2-methyloxazoline), polyamide, polyenol, polyene acid, polyphosphate, polyether derivative, polyamino acid derivative, poly(2-methyloxazoline) derivative, poly(2-methyloxazoline) derivative, polyamide derivative, polyenol derivative, polyene acid derivative and polyphosphate derivative; the polyether in the polyether and polyether derivative independently preferably includes one or more of polyethylene glycol, oligomer (ethylene glycol) (oligoEG), oligomer (ethylene glycol) derivative, polyethylene glycol methyl ether acrylate (mPEGA) and polyethylene glycol methyl ether methacrylate (mPEGMA); the polyamino acid in the polyamino acid and polyamino acid derivative independently preferably includes poly-L-glutamic acid (PGA), poly-L-lysine (PLL) and poly-L- One or more of lysine derivatives; the polyamide preferably includes polyacrylamide and poly-N-isopropylacrylamide; the polyalkenoic acid and the polyalkenoic acid derivatives independently preferably include polyacrylic acid and polymethyl acrylate; the polyalkenoic alcohol and the polyalkenoic alcohol derivatives independently preferably include polyvinyl alcohol and polyvinyl cinnamate. In the present invention, the hydrophobic polymer block preferably includes one or more of polyester, polycarbonate, polyethylene, polybutadiene, polylactic acid, polylactic acid-polyglycolic acid, polydimethylsiloxane (PDMS), polymethyl methacrylate (PMMA), polystyrene (PSt), polyester derivatives, polycarbonate derivatives, polyethylene derivatives, polybutadiene derivatives, polylactic acid derivatives, polylactic acid-polyglycolic acid derivatives, polydimethylsiloxane derivatives, polymethyl methacrylate derivatives and polystyrene derivatives; the polyester in the polyester and polyester derivatives independently preferably includes one or more of polycaprolactone (PCL), polylactide (PLA), polylactide-glycolide (PLGA) and polydecanoic acid (PDL); the polycarbonate in the polycarbonate and polycarbonate derivatives independently preferably includes polytrimethylene carbonate (PTMC), poly(2,4,6-trimethoxybenzylidene pentaerythritol carbonate) (PTMBPEC) and poly(2,4,6-trimethoxybenzylidene pentaerythritol carbonate) (PTMBPEC) and poly(2,4,6-trimethoxybenzylidene pentaerythritol carbonate) (PTMBPEC). One or more of trimethoxybenzylidene pentaerythritol carbonate) derivatives.In the present invention, the amphiphilic block copolymer preferably includes poly (ethylene glycol) - polycaprolactone copolymer (PEG-PCL), poly (ethylene glycol) - polylactic acid copolymer (PEG-PLA), poly (ethylene glycol) - polylactic acid - polyglycolic acid copolymer (PEG-PLGA) or poly (ethylene glycol) - polydecanoic acid copolymer (PEG-PDL), more preferably poly (ethylene glycol) - polycaprolactone copolymer or poly (ethylene glycol) - polylactic acid copolymer.

[0051] In the present invention, the mass percentage of the hydrophilic polymer block is 20 to 50%, preferably 25 to 45%, and more preferably 28 to 34%. In the present invention, the mass percentage of the hydrophilic polymer block in the amphiphilic block copolymer is the value of the weight average molecular weight of the hydrophilic polymer block in the amphiphilic block copolymer divided by the weight average molecular weight of the amphiphilic block copolymer multiplied by 100%.

[0052] In the present invention, the weight average molecular weight of the amphiphilic block copolymer is preferably 4 to 100 KDa, preferably 5 to 40 KDa, and more preferably 7 to 15 KDa; the weight average molecular weight of the hydrophilic polymer block is 2 to 20 KDa, preferably 2 to 10 KDa, and more preferably 3 to 5 KDa; the weight average molecular weight of the hydrophobic polymer block is preferably 2 to 80 KDa, preferably 3 to 30 KDa, and more preferably 5 to 15 KDa.

[0053] The present invention has no special requirements for the preparation method of the amphiphilic block copolymer, and conventional methods in the art can be used. Specifically, the amphiphilic block copolymer is synthesized by a ring-opening polymerization method, mPEG-OH is selected as an initiator, stannous isooctanoate is used as a catalyst, the ε-caprolactone monomer is induced to open the ring, and the mixture is heated at 110° C. for 24 hours under anhydrous and oxygen-free conditions, and purified by ether precipitation to obtain a PEG-PCL copolymer.

[0054] In the present invention, the polymer-encapsulated lipid nanoparticles include lipids encapsulated in the polymer vesicles, and the lipids include cationic lipids; the cationic lipids preferably include (2,3-dioleoyl-propyl)-trimethylammonium chloride (DOTAP), dioleoylpropyl trimethylammonium chloride (DOTMA), ethyl phosphatidylcholine (ethyl PC), 3β-[N- (N', N'-dimethylaminoethane)-carbamoyl] cholesterol (DC-cholesterol), N4-cholesterol-spermidine (GL67), 1,2-dioloxy-3-dimethylaminopropane (DODMA), trimethyl-2,3-oleoyloxypropylammonium bromide (DOTAP), dimethyl-2,3-dioleyloxypropyl-2-(2-sperminecarboxamido)ethylammonium trifluoroacetate (DOSPA), trimethyldodecylammonium bromide (DTAB), trimethyltetradecylammonium bromide (TTAB), trimethylhexadecylammonium bromide (CTAB), dimethyldioctadecylammonium bromide (DDAB), dimethyl-2-hydroxyethyl-2,3-dioleyloxyl ammonium bromide (DORI), dimethyl-2-hydroxyethyl-2,3-dioleyloxyl ammonium bromide (DORIE) , dimethyl-3-hydroxypropyl-2,3-dioleyloxy ammonium bromide (DORIE-HP), dimethyl-4-hydroxybutyl-2,3-dioleyloxy ammonium bromide (DORIE-HB), dimethyl-1-hydroxypentyl-2,3-dioleyloxy ammonium bromide (DORIE-HPc), dimethyl-2-hydroxyethyl-2,3-dihexadecyloxy propyl ammonium bromide (DPRIE), dimethyl-2-hydroxyethyl-2,3-dioctadecyloxy propyl ammonium bromide (DSRIE), D-Lin-MC3-DMA, one or more, more preferably (2,3-dioleoyl-propyl)-trimethylammonium chloride (DOTAP). In the present invention, the lipid preferably also includes an auxiliary lipid, and the auxiliary lipid preferably includes one or more of phosphatidylethanolamine (PE), dioleoylphosphatidylcholine (DOPC), phosphatidylcholine (PC), cholesterol and dioleoylphosphatidylethanolamine (DOPE).

[0055] In the present invention, the molar ratio of the amphiphilic block copolymer and the lipid is preferably 0.01 to 1:1, preferably 0.04 to 0.7:1, more preferably 0.06 to 0.65:1, further preferably 0.08 to 0.5:1, and most preferably 0.093 to 0.3:1; the mass ratio of the amphiphilic block copolymer and the lipid is preferably 0.1 to 50:1, preferably 0.86 to 10.7:1, more preferably 1.3 to 6.5:1, further preferably 2 to 5:1, and most preferably 3 to 4:1.

[0056] In the present invention, the polymer-encapsulated lipid nanoparticles preferably further include a stabilizer, and the stabilizer is preferably encapsulated inside the PE-LNP and / or located outside the PE-LNP. In the present invention, the stabilizer preferably includes one or more of a carbohydrate, a polyol, a surfactant, a pharmaceutically acceptable complex, and a pharmaceutically acceptable salt, and the carbohydrate is preferably a carbohydrate; the carbohydrate preferably includes one or more of a monosaccharide, an oligosaccharide, and a polysaccharide, and more preferably includes trehalose, sucrose, L-arabinose, D-ribose, D-xylose, glucose, galactose, dextran, mannitol, lactitol, fructose, lactose, mannobiose, isomaltose, mannose, xylitol, sorbitol, raffinose, maltitol, α-pyritol, One or more of glucopyranosyl 1-6-mannitol, maltooligosaccharides, glycogen, starch, cellulose, chitosan and chitin, more preferably trehalose or dextran; the polyol preferably includes one or more of D-sorbitol, polyethylene glycol 2000 and octadecyl alcohol; the surfactant preferably includes one or more of polysorbate 20, polysorbate 80, polyvinyl alcohol and poloxamer 188; the pharmaceutically acceptable complex preferably includes hydrogenated castor oil; the pharmaceutically acceptable salt preferably includes sodium carboxymethyl starch and / or sodium octanoate.

[0057] In the present invention, when the sugar is encapsulated inside the lipid nanoparticles; the mass ratio of the sugar to the lipid is preferably 0.25-625:1, more preferably 0.5-100:1, and further preferably 0.65-10:1; in the present invention, when the sugar is coated on the outside of the lipid nanoparticles; the mass ratio of the sugar to the lipid is preferably 0.25-10000:1, more preferably 100-5000:1, and further preferably 125-1000:1; in the present invention, when The carbohydrate is partially encapsulated inside the lipid nanoparticles and partially coated on the outside of the lipid nanoparticles; the mass ratio of the carbohydrate to the lipid encapsulated inside the lipid nanoparticles is preferably 0.25-625:1, more preferably 0.5-100:1, and further preferably 0.65-10:1; the mass ratio of the carbohydrate to the lipid coated on the outside of the lipid nanoparticles is preferably 0.25-10000:1, more preferably 100-5000:1, and further preferably 125-1000:1.

[0058] In the present invention, the polymer-encapsulated lipid nanoparticles preferably further include a targeting ligand, which is preferably located on the outer surface of the polymer vesicle, specifically, coupled to the hydrophilic end group of the amphiphilic block copolymer; the targeting ligand preferably includes peptides, proteins, aptamers, carbohydrates, folic acid, antibodies, fragments that can bind to antigens, vitamins or their derivatives; the peptides include G protein coupled receptors (GCR), Arg-Gly-Asp (RGD) or their derivatives; the proteins preferably include lectins, lactoferrin, transferrin or their derivatives; the aptamers preferably include RNA aptamers for HIV glycoprotein or their derivatives; the carbohydrates are the same as the aforementioned carbohydrates, which will not be repeated here, and the carbohydrates are more preferably mannose, glucose, galactose or their derivatives; the antibodies and fragments that can bind to antigens independently preferably include monoclonal or polyclonal, more preferably anti-Her2 antibodies, anti-EGFR antibodies or their derivatives; the vitamins are preferably vitamin D. The present invention does not specifically limit the amount of the targeting ligand, which is subject to meeting the targeting function requirements.

[0059] In the present invention, the amphiphilic block copolymer is biodegradable and biocompatible, and the amphiphilic block copolymer as the shell of lipid nanoparticles can well accommodate and protect the load. In addition, the outer layer of the amphiphilic block copolymer has high mechanical strength, and enhances the stability of the lipid nanoparticles themselves and the load, promoting the effectiveness of its in vivo application and the stability of in vitro storage.

[0060] In the present invention, the particle size of the polymer-encapsulated lipid nanoparticles is preferably ≤1 μm, more preferably 50 nm to 200 nm, and most preferably 50 nm to 150 nm; the Zeta potential of the polymer-encapsulated lipid nanoparticles is preferably >0 mV, more preferably ≥+10 mV, and most preferably +40 to +60 mV.

[0061] The lipid nanoparticles containing the amphiphilic block copolymer vesicle structure provided by the present invention can improve the stability of the load (saRNA), and can stably store the load in the lipid nanoparticles at 2 to 8° C. for 30 days. In the present invention, when the polymer-encapsulated lipid nanoparticles include sugars, the transfection efficiency and stability of the load (saRNA) can be further improved, and the storage time of the lipid nanoparticles loaded with the load at 2 to 8° C. can be further extended, and at the same time, it can be stably stored at a higher temperature (40° C.) for two weeks.

[0062] The present invention also provides a method for preparing the polymer-encapsulated lipid nanoparticles described in the above technical solution, comprising the following steps:

[0063] Dissolving the amphiphilic block copolymer and lipid in an organic solvent to obtain an organic phase; the mass percentage of the hydrophilic polymer block in the amphiphilic block copolymer is 20-50%; the lipid includes a cationic lipid;

[0064] The organic phase is mixed with water for self-assembly coating, and the organic solvent is removed to obtain the polymer-coated lipid nanoparticles.

[0065] The present invention dissolves the amphiphilic block copolymer and the lipid in an organic solvent to obtain an organic phase. In the present invention, the organic solvent preferably includes tetrahydrofuran (THF). In the present invention, the mass ratio of the amphiphilic block copolymer and the lipid is preferably 0.86 to 10.7: 1, more preferably 1.3 to 2.6: 1. The present invention has no particular limitation on the amount of the organic solvent, as long as the amphiphilic block copolymer and the lipid can be completely dissolved. In the present invention, the types and ratios of the amphiphilic block copolymer and the lipid are described in the above-mentioned technical solution, and will not be repeated here.

[0066] After obtaining the organic phase, the present invention mixes the organic phase with water and then performs self-assembly coating, removes the organic solvent, and obtains the polymer-coated lipid nanoparticles. In the present invention, when the polymer-coated lipid nanoparticles also include a stabilizer, the stabilizer is preferably dissolved in water to obtain an aqueous phase, and the organic phase is mixed with the aqueous phase before self-assembly coating. In the present invention, the mass ratio of the stabilizer in the aqueous phase to the amphiphilic block copolymer in the organic phase is preferably 0.01 to 160:1, more preferably 0.38 to 20:1; further preferably 0.74 to 1.54:1. In the present invention, the mixing method is not particularly limited as long as the raw materials can be mixed evenly. In the present invention, the temperature of the self-assembly is preferably 4 to 25°C, more preferably 15 to 20°C; the time of the self-assembly is preferably 1 to 10 min, more preferably 2 to 5 min. In the present invention, the self-assembly is preferably carried out under stirring conditions, and the stirring speed is preferably 100 to 300 r / min, more preferably 190 to 200 r / min. In the present invention, the method for removing the organic solvent is preferably evaporation, and the evaporation is preferably carried out in a fume hood or a rotary evaporator; when the evaporation is carried out in a rotary evaporator, the evaporation temperature is preferably 30-37°C; when the evaporation is carried out in a fume hood, the evaporation temperature is preferably 30-40°C, more preferably 35-37°C; the evaporation time is preferably 5-10 min, more preferably 6-8 min.

[0067] In the present invention, when the polymer-encapsulated lipid nanoparticles include a stabilizer, the present invention preferably provides three preparation methods according to the different distribution positions of the stabilizer:

[0068] I. When the stabilizer is encapsulated inside the polymer-encapsulated lipid nanoparticles, the preparation method of the polymer-encapsulated lipid nanoparticles preferably includes the following steps: dissolving the amphiphilic block copolymer and the lipid in an organic solvent to obtain an organic phase; dissolving the stabilizer in water to obtain an aqueous phase; mixing the organic phase and the aqueous phase, performing self-assembly coating, and removing the organic solvent to obtain the polymer-encapsulated lipid nanoparticles. In the present invention, the preparation of the organic phase is preferably prepared according to the above method, which is not repeated here. In the present invention, the mass ratio of the stabilizer in the aqueous phase to the amphiphilic block copolymer in the organic phase is preferably 0.01 to 160:1, more preferably 0.38 to 20:1; further preferably 0.74 to 1.54:1. In the present invention, the volume ratio of the organic phase to the aqueous phase is preferably 0.1 to 10:1, more preferably 0.5 to 1:1. In the present invention, the self-assembly is preferably carried out according to the above preparation conditions, which is not repeated here. After the self-assembly coating, the present invention preferably further comprises removing the organic solvent in the self-assembly coating system. The present invention has no special limitation on the method for removing the organic solvent, and a removal method well known to those skilled in the art can be used, such as rotary evaporation.

[0069] II. When the stabilizer is only outside the polymer-coated lipid nanoparticles, the polymer-coated lipid nanoparticles are preferably present in a solution or lyophilized form; the method for preparing the polymer-coated lipid nanoparticles preferably comprises the following steps: dissolving the amphiphilic block copolymer and lipids in an organic solvent to obtain an organic phase; mixing the organic phase and the aqueous phase, and self-assembling and coating the polymer and lipid to obtain an assembled polymer-coated lipid nanoparticle solution; dissolving the stabilizer in the prepared polymer-coated lipid nanoparticle solution to obtain polymer-coated lipid nanoparticles with the stabilizer only on the outside. In the present invention, the concentration of the stabilizer in the mixed solution of the self-assembly solution and the stabilizer is preferably 30 to 400 mg / mL, more preferably 200 to 250 mg / mL. The present invention preferably prepares the organic phase according to the above method, which will not be repeated here. The self-assembly of the present invention is preferably carried out according to the above method, which will not be repeated here. When in a freeze-dried form, after the self-assembly coating, the present invention preferably further comprises freeze-drying the self-assembly coating system to obtain a polymer-encapsulated lipid nanoparticle freeze-dried powder; the removal of the organic solvent is preferably carried out according to the above method, which will not be repeated here; the freezing temperature is preferably -196 to 0°C, optimally -80 to -50°C. The present invention has no special limitation on the freeze-drying time, as long as the water can be completely freeze-dried.

[0070] III. When the stabilizer is partially encapsulated inside the lipid nanoparticles and partially encapsulated outside the lipid nanoparticles, the polymer-encapsulated lipid nanoparticles are preferably present in a solution or lyophilized form; the method for preparing the polymer-encapsulated lipid nanoparticles preferably includes the following steps: dissolving the amphiphilic block copolymer and lipids in an organic solvent to obtain an organic phase; dissolving part of the stabilizer in water to obtain an aqueous phase; mixing the organic phase and the aqueous phase for self-assembly coating, removing the organic phase to obtain assembled polymer-encapsulated lipid nanoparticles with partial sugar encapsulation inside; dissolving the remaining stabilizer and mixing with the assembled polymer-encapsulated lipid nanoparticles with partial sugar encapsulation inside to obtain a liquid form of the polymer-encapsulated lipid nanoparticles. The resulting mixed solution is lyophilized to obtain its lyophilized form. The present invention preferably prepares the organic phase according to the above method, which is not repeated here. The present invention preferably prepares the aqueous phase according to the above method, which is not repeated here. In the present invention, the mass ratio of the stabilizer in the aqueous phase to the amphiphilic block copolymer in the organic phase is preferably 0.01 to 160:1, more preferably 0.38 to 20:1; further preferably 0.74 to 1.54:1; the volume ratio of the organic phase to the aqueous phase is preferably 0.1 to 10:1, more preferably 0.5 to 1:1. The present invention preferably performs self-assembly coating according to the above method, which will not be repeated here. In the present invention, the concentration of the stabilizer in the mixed solution is preferably 30 to 400 mg mL -1 , more preferably 200 to 250 mg mL -1 In the present invention, the freeze-drying is preferably carried out under the same conditions as the aforementioned freeze-drying, which will not be described in detail herein.

[0071] In the present invention, when the polymer-coated lipid nanoparticles further include a targeting ligand, the method for preparing the polymer-coated lipid nanoparticles preferably includes method one and method two.

[0072] In the present invention, the method 1 preferably includes the following steps: mixing the targeting ligand and the amphiphilic block copolymer and then chemically coupling to obtain the targeting ligand-amphiphilic block copolymer; dissolving the targeting ligand-amphiphilic block copolymer and lipid in an organic solvent to obtain an organic phase; the mass percentage of the hydrophilic polymer block in the targeting ligand-amphiphilic block copolymer is 20-50%; the lipid includes a cationic lipid; mixing the organic phase with water and then self-assembling and coating, removing the organic solvent, and obtaining polymer-coated lipid nanoparticles containing targeting ligands on the surface. The present invention has no special limitation on the chemical coupling, which can be based on not destroying the structure of the polymer-coated lipid nanoparticles and satisfying the chemical targeting effect after the coupling of the targeting ligand. The present invention preferably prepares polymer-coated lipid nanoparticles according to the above method, which will not be repeated here.

[0073] In the present invention, the second method preferably comprises the following steps: mixing the polymer-coated lipid nanoparticles with the targeting ligands and then chemically coupling them to obtain polymer-coated lipid nanoparticles with the targeting ligands on their surfaces. The present invention has no particular limitation on the chemical coupling, which can be based on not destroying the structure of the polymer-coated lipid nanoparticles and satisfying the chemical targeting effect after coupling with the targeting ligands.

[0074] The present invention also provides a pharmaceutical preparation, comprising polymer-coated lipid nanoparticles and a load; the polymer-coated lipid nanoparticles are polymer-coated lipid nanoparticles as described in the above technical solution or polymer-coated lipid nanoparticles prepared by the preparation method as described in the above technical solution; the load comprises nucleic acid, and the nucleic acid preferably comprises one or more of DNA, RNA and plasmid; the RNA preferably comprises messenger RNA (mRNA), self-replicating RNA (saRNA) or small interfering RNA (siRNA), and the molecular weight of the RNA is preferably 10 to 20,000 nt, more preferably 1,000 to 10,000 nt, and further preferably 5,000 to 9,500 nt. In the present invention, the nucleic acid is bound to the lipid in the polymer-coated lipid nanoparticle by electrostatic force. In the present invention, the load preferably also includes peptides, proteins, antibodies, monosaccharides, disaccharides, polysaccharides, small molecule hydrophobic drugs or small molecule hydrophilic drugs. The present invention does not specifically limit the types of the peptides, proteins, antibodies, monosaccharides, disaccharides, polysaccharides, small molecule hydrophobic drugs or small molecule hydrophilic drugs. Peptides, proteins, antibodies, monosaccharides, disaccharides, polysaccharides, small molecule hydrophobic drugs or small molecule hydrophilic drugs well known to those skilled in the art can be used. In the present invention, the mass ratio of the amphiphilic block copolymer and the load in the polymer-encapsulated lipid nanoparticles is preferably 5 to 500:1, more preferably 20 to 80:1, and further preferably 40 to 65:1. In the present invention, when the load is a nucleic acid, the nitrogen-phosphorus molar ratio of the pharmaceutical preparation is preferably 2 to 100, more preferably 3 to 50, further preferably 10 to 15, and most preferably 11.

[0075] In the present invention, the loading substance preferably further includes peptides, proteins, antibodies, monosaccharides, disaccharides, polysaccharides, small molecule hydrophobic drugs or small molecule hydrophilic drugs, more preferably peptides, small molecule hydrophobic drugs or small molecule hydrophilic drugs.

[0076] In the present invention, the preparation process of RNA-loaded polymer-encapsulated lipid nanoplasmids (PE-LNPs) and the schematic diagram of intracellular delivery of saRNA mediated by polymer-encapsulated lipid nanoplasmids are as shown in Figure 1As shown, A is a schematic diagram of the preparation process of RNA-loaded polymer-encapsulated lipid nanoparticles (PE-LNPs), and B is a schematic diagram of the intracellular delivery of saRNA mediated by polymer-encapsulated lipid nanoplasmids. In the present invention, the intracellular delivery process is: PE-LNP is transported to the endosome after being endocytosed by the cell, and the positively charged PE-LNP will break through the endosomal barrier and transfer to the cytoplasm due to the proton sponge effect, avoiding being transported to the lysosome and then degraded.

[0077] In the present invention, the preparation method of the pharmaceutical preparation is preferably consistent with the preparation method of polymer-coated lipid nanoparticles, except that the organic phase is mixed with the load aqueous solution before self-assembly coating, or the load is directly mixed with the polymer-coated lipid nanoparticles and adsorbed to the surface of the polymer-coated lipid nanoparticles by electrostatic adsorption. In the present invention, the utensils used for dissolution are preferably treated before dissolution to ensure that the utensils do not contain ribonucleases (RNase). In the present invention, the water preferably does not contain ribonucleases. In the present invention, the concentration of the load aqueous solution is preferably 0.1 to 500 μg / mL, more preferably 10 to 40 μg / mL. In the present invention, the volume ratio of the load aqueous solution to the organic phase is preferably 0.1 to 10:1, more preferably 0.5 to 1:1.

[0078] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0079] Example 1

[0080] 650 μg PEG 2K -PCL 5K and 250 μg of DOTAP were dissolved in 0.5 mL of THF to obtain an organic phase;

[0081] The organic phase was stirred at 200 r / min at 25° C. for 2 minutes for self-assembly coating, and then stirred at 20° C. for 8 minutes in a fume hood to obtain polymer-coated lipid nanoparticles.

[0082] Embodiments 2 to 15

[0083] Polymer-coated lipid nanoparticles were prepared according to the method of Example 1, except that the mass ratio of the hydrophilic polymer block to the hydrophobic polymer block in the amphiphilic block copolymer was set according to Table 1; the mass ratio and molar ratio of the amphiphilic block copolymer and the lipid were set according to Table 1.

[0084] Table 1 Types of amphiphilic block copolymers and ratios of amphiphilic block copolymers and lipids in Examples 1 to 15

[0085]

[0086]

[0087] The polymer-encapsulated lipid nanoparticles prepared in Examples 1 to 2 and Examples 4 to 5 were observed by transmission electron microscopy to obtain TEM images, as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the polymer-encapsulated lipid nanoparticles provided by the present invention have a core-shell structure.

[0088] In the present invention, unless otherwise specified, the polymer used is PEG 5k -PCL 10k , the lipid is DOTAP, and the polymer-encapsulated lipid nanoparticles loaded with RNA are referred to as PE-LNPm-n, where m represents the N / P molar ratio and n represents the mass ratio of the amphiphilic block copolymer and RNA.

[0089] Example 16

[0090] Using Sn(Oct2) as catalyst, methoxy polyethylene glycol (mPEG-OH) initiated the ring-opening polymerization of ε-CL to synthesize PEG-PCL copolymers. Specifically, 200 mg mPEG 2K -OH, 530 mg ε-CL and 50 mg Sn(Oct)2 were dissolved in 5 mL anhydrous toluene, heated to 110 °C in a dry nitrogen atmosphere, and reacted for 48 h. After the reaction, the mixture was degassed and cooled to room temperature. The resulting product was then precipitated with supercooled ether. The polymer was filtered and vacuum dried to constant weight at room temperature to obtain PEG 2K -PCL 5K Polymer; GPC test shows that the PEG 2K -PCL 5K The weight average molecular weight of the polymer is 9059 Da, with a relatively low polydispersity of 1.59;

[0091] 650 μg PEG 2K -PCL 5K and 250 μg of DOTAP were dissolved in 0.5 mL of THF to obtain an organic phase;

[0092] The apparatus was treated to ensure the absence of RNase, and 10 μg of saRNA (luciferase self-replicating RNA) was dissolved in 1 mL of RNase-free water to obtain a loading solution;

[0093] The organic phase and the load solution are mixed, stirred at a speed of 200 r / min at 25° C. for self-assembly coating for 2 minutes, and then stirred at room temperature in a fume hood for 8 minutes to obtain polymer-coated lipid nanoparticles loaded with saRNA; the nitrogen-phosphorus ratio of the polymer-coated lipid nanoparticles loaded with saRNA is 11, and the mass ratio of the amphiphilic block copolymer and saRNA in the polymer-coated lipid nanoparticles loaded with saRNA is 65:1; the polymer-coated lipid nanoparticles loaded with saRNA are referred to as PE-LNP 11-65.

[0094] Embodiment 17

[0095] The polymer-encapsulated lipid nanoparticles loaded with saRNA were prepared according to Example 16, except that the nitrogen-phosphorus ratio of the polymer-encapsulated lipid nanoparticles loaded with saRNA was 5; the polymer-encapsulated lipid nanoparticles loaded with saRNA were referred to as PE-LNP 5-65.

[0096] Embodiment 18

[0097] The polymer-encapsulated lipid nanoparticles loaded with saRNA were prepared according to Example 16, except that the nitrogen-phosphorus ratio of the polymer-encapsulated lipid nanoparticles loaded with saRNA was 18; the polymer-encapsulated lipid nanoparticles loaded with saRNA were referred to as PE-LNP 18-65.

[0098] Embodiment 19

[0099] The polymer-encapsulated lipid nanoparticles loaded with saRNA were prepared according to Example 18, except that the mass ratio of the amphiphilic block copolymer and saRNA in the polymer-encapsulated lipid nanoparticles loaded with saRNA was 80:1; the polymer-encapsulated lipid nanoparticles loaded with saRNA were referred to as PE-LNP 18-80.

[0100] Embodiment 20

[0101] PEG-PCL copolymers were synthesized by using stannous isooctanoate (Sn(Oct)2) as catalyst and methoxy polyethylene glycol (mPEG-OH) as the initiator of ε-CL ring-opening polymerization. Specifically, 200 mg mPEG 5K -OH, 470 mg ε-CL and 50 mg Sn(Oct)2 were dissolved in 5 mL anhydrous toluene, heated to 110 °C in a dry nitrogen atmosphere, and reacted for 48 h. After the reaction, the mixture was degassed and cooled to room temperature. The resulting product was then precipitated with supercooled ether. The polymer was filtered and vacuum dried to constant weight at room temperature to obtain PEG 5K -PCL 10KPolymer; GPC test shows that the PEG 5K -PCL 10K The weight average molecular weight of the polymer is 10680 Da, with a relatively low polydispersity of 1.52;

[0102] The polymer-coated lipid nanoparticles loaded with saRNA were prepared according to the method of Example 16, except that PEG 2K -PCL 5K Polymer replaced with PEG 5K -PCL 10K Polymer; the lipid nanoparticles wrapped by the polymer loaded with saRNA are referred to as PE-LNP 11-65.

[0103] The prepared PEG was treated in deuterated chloroform (CDCl3) 5K -PCL 10K The polymer was subjected to NMR detection to obtain an NMR spectrum ( 1 H-NMR) Figure 2 As shown. Figure 2 It can be seen that PEG was prepared 5K -PCL 10K polymer.

[0104] Embodiment 21

[0105] The polymer-encapsulated lipid nanoparticles loaded with saRNA were prepared according to Example 20, except that the nitrogen-phosphorus ratio of the polymer-encapsulated lipid nanoparticles loaded with saRNA was 5; the polymer-encapsulated lipid nanoparticles loaded with saRNA were referred to as PE-LNP 5-65.

[0106] Embodiment 22

[0107] The polymer-encapsulated lipid nanoparticles loaded with saRNA were prepared according to Example 20, except that the nitrogen-phosphorus ratio of the polymer-encapsulated lipid nanoparticles loaded with saRNA was 18; the polymer-encapsulated lipid nanoparticles loaded with saRNA were referred to as PE-LNP 18-65.

[0108] Embodiment 23

[0109] The polymer-encapsulated lipid nanoparticles loaded with saRNA were prepared according to Example 22, except that the mass ratio of the amphiphilic block copolymer and saRNA in the polymer-encapsulated lipid nanoparticles loaded with saRNA was 80:1; the polymer-encapsulated lipid nanoparticles loaded with saRNA were referred to as PE-LNP 18-80.

[0110] Test Example 1

[0111] The particle size distribution (Z-average) and zeta potential (based on the Smulochowski model) of the PE-LNPs prepared in Examples 16 to 23 were measured using a Zetasizer μV instrument (Malvern, UK) and zetaPALS, respectively, as shown in Table 2. The particle size distribution of the PE-LNPs prepared in Example 23 is shown in Table 2. Figure 3 The polydispersity index (PDI) results of the PE-LNPs prepared in Examples 16 to 23 are shown in Table 2.

[0112] Table 2 Particle size distribution, zeta potential and polydispersity index of PE-LNPs prepared in Examples 16 to 23

[0113]

[0114] Depend on Figure 3 It can be seen that PE-LNP loaded with saRNA is monodisperse.

[0115] As shown in Table 2, PEG 5K -PCL 10K The assembled PE-LNPs showed an average particle size of 113.1±0.3~134.2±0.6 nm and a low PDI of 0.21±0.03~0.35±0.02. 2K -PCL 5K The PE-LNPs composed of PEG showed larger size (133.9±0.5~149.6±0.4nm) and higher PDI (0.49±0.09~0.59±0.10). 5K -PCL 10K Self-assembled PE-LNPs exhibited a more stable structure, which may be attributed to the longer hydrophilic PEG chain length and thicker polymer vesicle layer. The nitrogen-phosphorus molar ratio (N / P ratio) is a key factor controlling the saRNA loading capacity and endosomal escape efficiency. As the N / P ratio increases from 5 to 18, the PEG 5K -PCL 10K The zeta potential of PE-LNPs composed of (polymer / saRNA weight ratio = 65) increased significantly from +29.0 ± 0.9 mV to +44.5 ± 0.8 mV due to the increase of cationic lipids. However, when the polymer / saRNA weight ratio in PE-LNPs increased from 65 to 80, the zeta potential of PE-LNPs composed of PEG 5K -PCL 10K The zeta potential of PE-LNPs composed of (N / P=18) decreased from +44.5±0.8mV to +40.2±0.9mV, which may be due to the enhanced shielding effect of the polymer vesicle layer.2K -PCL 5K The synthesized PE-LNPs showed the same trend.

[0116] Test Example 2

[0117] Electron microscopy structural characterization

[0118] The morphology of the PE-LNPs prepared in Examples 1-2 and Examples 4-5 was observed using a scanning electron microscope. A drop of the PE-LNPs suspension was dropped onto a copper mesh. After the sample was dried, it was gold-plated by ion sputtering. Subsequently, a JSM-6400 scanning electron microscope (JEOL Ltd, Tokyo, Japan) was used to observe the sample at an accelerating voltage of 20 kV to obtain a SEM image, as shown in FIG4 .

[0119] PE-LNPs samples for cryo-TEM (Tecnai F20 G2 at 200 kV) were prepared on carbon-coated copper grids (StructureProbe corporation, PA) using a semi-automated Vitrobot (Vitrobot Mark II, FEI). The specific steps are as follows: 4 μL of 1 mg / mL PE-LNPs solution was cast on the carbon grid, and then the grid was transferred to the Vitrobot chamber with a humidity of 100% and a temperature of 20°C. After absorbing for 1 s, the grid was quickly immersed in liquid ethane to effectively vitrify the sample. The sample was stored at -170°C using a Gatan 626 cryogenic container until it was successfully transferred to the cryo-tem instrument for observation, and the cryo-tem image was obtained, as shown in the figure. Figure 4 shown.

[0120] Figure 4 ' PE-LNP 5'-65', PE-LNP 11'-65', PE-LNP 18'-65' and PE-LNP18'-80' marked with ' respectively represent samples having the same composition as PE-LNP 5-65, PE-LNP 11-65, PE-LNP 18-65 and PE-LNP 18-80 but not containing saRNA. Figure 4It can be seen that PE-LNP shows a clear outer layer. The amphiphilic PEG-PCL polymer can self-assemble into a polymersome structure containing a hydrophilic core. The darker outer layer should be attributed to the hydrophobic PCL polymer with higher contrast. There are many black spots in the core, which are aggregated DOTAP lipid nanoparticles. DOTAP is amphiphilic, with the polar part being hydrophilic and the nonpolar part being hydrophobic as the hydrophobic part having hydrophobic properties. Since the internal PEG-PCL vesicle structure is hydrophilic, the "hydrophobic effect" of the DOTAP tail (whose role is to minimize the contact between the aliphatic tail and the water environment) together with other tails (including van der Waals interactions and hydrogen bonding of the hydrophilic head group) determine the self-assembly behavior of DOTAP. Therefore, the black spots showing darker contrast due to poor electron penetration may be composed of unsaturated hydrophobic hydrocarbon tails present in DOTAP. Therefore, DOTAP self-assembles into "sponge-like" aggregates that are encapsulated in the hydrophilic core of the polymersome and divide the internal space into subcompartments through the hydrophobic interactions of the hydrocarbon tails. Compared with liposomes and polymer vesicles, the internal structure of PE-LNPs provides a significantly higher surface area, which is beneficial for the entrapment of nucleic acids. In addition, the PEG-PCL shell not only prevents RNA degradation but also improves the stability of the PE-LNP system due to its higher mechanical strength than the lipid bilayer.

[0121] Test Example 3

[0122] saRNA encapsulation efficiency assay

[0123] RiboGreen Assay (Quant-iT TM RiboGreen TM RNA Assay Kit, Thermo Fisher) was used to determine the saRNA encapsulation efficiency. TE buffer and RiboGreen aqueous solution were prepared according to the manufacturer's instructions, containing 0.5% TritonX-100 and 0.5% Triton X-100, respectively. A calibration curve of fluorescence intensity versus saRNA concentration was established. The samples were diluted to an appropriate concentration with TE buffer without TritonX-100, mixed with Triton X-100 free RiboGreen working solution, and incubated in the dark for 15 minutes. The samples were then pipetted into a 96-well black plate, with each well containing 200 μL of the final mixture. The fluorescence spectrophotometer ( The fluorescence intensity was measured at excitation and emission wavelengths of 480 and 520 nm, respectively, using a Discover Microplate Reader (Promega, USA) and repeated three times to determine the free saRNA concentration (C unloadedA similar method was used to measure total saRNA concentration (C) using TE buffer and RiboGreen working solution containing 0.5% Triton X-100. total ) to dissolve the nanoparticles. The encapsulation efficiency was calculated according to formula (1):

[0124] Encapsulation efficiency (%) = (1-C unloaded / C total )×100 Formula (1).

[0125] The encapsulation efficiency of PE-LNP 11-65 was calculated to be 93.6±3.2%, indicating that the polymer-encapsulated lipid nanoparticles have a high RNA loading capacity.

[0126] Test Example 4

[0127] Structural Elucidation by Fluorescence Resonance Energy Transfer (FRET)

[0128] FRET experiments were performed on PE-LNPs using a fluorescence spectrophotometer (Microplate Flash Reader, PerkinElmer, Waltham, MA, USA). N-(7-nitro-2-1,3-benzoxadiazol-4-yl) -1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (NBD-PE) / N-(lissamine rhodamine Bsulfonyl)-1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (Rhod-PE) were used as a fluorescent donor / acceptor pair, respectively, with the excitation wavelength set at 460 nm and the emission spectra collected from 480 nm to 630 nm.

[0129] PE-LNPs encapsulating donor NBD-PE (4 mm) and acceptor Rhod-PE (4 mm) were prepared. For different PE-LNPs without saRNA loading (PE-LNP 5'-65', PE-LNP11'-65' and PE-LNP18'-65'), NBD-PE and Rhod-PE were co-dissolved in 0.5 mL THF (containing pre-dissolved PEG-PCL and DOTAP) at the desired ratio and then quickly mixed with 1 mL H2O. Stir at room temperature for 1 to 2 minutes, and then remove THF by rotary evaporation. A control group without polymer (i.e., DOTAP liposomes) was prepared for comparison. The molar concentration of DOTAP in the control group liposomes was the same as the molar concentration of DOTAP in the corresponding PE-LNPs (or the total molar concentration of PEG-PCL and DOTAP). DOTAP and PEG 5k -PCL 10k The molar concentrations in PE-LNP 5'-65' were 143mmol / L and 43mmmol / L, respectively. The control liposomes were denoted as DOTAP-143 and DOTAP-186, respectively. In addition, only the donor (NBD-PE) labeled PE-LNPs, the FRET efficiency E was calculated according to formula (2):

[0130] E(%)=(I D -I DA ) / (I D )×100 Formula (2);

[0131] Among them, I D represents the fluorescence intensity of PE-LNPs labeled only with donor NBD-PE at 530 nm;

[0132] I DA Represents the fluorescence intensity of PE-LNPs simultaneously labeled with donor NBD-PE and acceptor NBD-PE at 530 nm.

[0133] Figure 5 Schematic diagram of the structure of a homogeneous polymer / lipid hybrid membrane (A) and diagrams of the structural verification process of the PE-LNP provided by the present invention (B-D). Figure 5 The schematic diagram of the homogeneous polymer / lipid hybrid membrane in A shows that the distance between NBD (donor dye) and Rhod (acceptor dye) is similar compared to the pure DOTAP lipid membrane with the same molar amount, so the fluorescence resonance energy transfer (FRET) efficiency on the homogeneous hybrid membrane should be similar to that on the homogeneous lipid membrane. Figure 5B to D in the figure are fluorescence spectra and FRET efficiencies of PE-LNP (PE-LNP 5'-65', PE-LNP 11'-65' and PE-LNP 18'-65') and DOTAP liposomes. The smaller numbers (143, 358 and 572) of DOTAP in each sample group represent the equivalent nanomoles of DOTAP present in the corresponding PE-LNP, respectively. The '-labeled PE-LNP 5'-65' represents a sample having the same composition as PE-LNP 5-65 but not containing saRNA. The larger numbers (i.e., 186, 401 and 615) of DOTAP in each sample group represent the total nanomoles of DOTAP and PEG5k-PCL10k present in the corresponding PE-LNP, respectively. NBD-PE (N-(7-nitrobenzene-2-oxa-1,3-diazol-4-yl)-1,2-cosanoyl-snglycero-3-phosphoethanolamine, triethylammonium salt) and Rhod-PE (2-dipalmitoyl-sn-glycero-3-phosphoethanolamine-N-(lissamine rhodamine B sulfonyl), ammonium salt) in PE-LNPs or DOTAP liposomes were immobilized at 4 mM.

[0134] The energy transfer efficiency between the donor fluorophore NBD (4.0 mM) and the acceptor fluorophore Rhod (4.0 mM) depends on their distance on the membrane layer. The most common structure formed after mixing the amphiphilic block copolymer with lipids is a hybrid vesicle structure with a homogeneous polymer / lipid hybrid membrane. Figure 5 As shown in Figure B, excitation of the donor NBD at 460 nm resulted in enhanced emission intensity of the acceptor Rhod in PE-LNP 5'-65', showing a FRET efficiency of 93.7 ± 0.2%. Assuming that PEG-PCL and DOTAP self-assemble into a uniform mixed film, the control DOTAP-186 liposomes should be at a similar level to PE-LNP 5'-65', since the FRET efficiency depends on the distance between the donor NBD and the acceptor Rhod, as shown in the schematic Figure 5 As shown in A. In fact, the FRET efficiency of PE-LNP 5'-65' is significantly higher than that of DOTAP-186 liposomes (85.9 ± 0.3%). Similarly, assuming that PEG-PCL and DOTAP self-assemble into a uniform mixed film, the FRET efficiency of the control DOTAP-143 liposomes (assembled by DOTAP at the same molar concentration as that present in PE-LNP 5'-65') should be higher than that of PE-LNP 5'-65' due to the shorter distance between the acceptor and the donor. However, it showed a similar FRET efficiency level to PE-LNP 5'-65' (92.9 ± 0.3%). Similar trends can be observed for PE-LNP 11'-65' and PE-LNP 18'-65', as shown in Figure 5 As shown in C to D. In summary, PE-LNP does not have a homogeneous polymer-lipid hybrid membrane structure.

[0135] In another experiment, PE-LNP11'-65' was labeled with NBD-PE (4.0mM) and Rhod-PE (4.0mM), respectively. Then, PE-LNP11'-65' (labeled with NBD-PE only) and PE-LNP11'-65' (labeled with Rhod-PE only) were mixed in equal volumes and stirred at 100r / min for 5min, 1h and 2h, respectively. The DOTAP liposomes in the control group were also labeled with NBD-PE (4.0mM) and Rhod-PE (4.0mM), respectively, and the molar concentration of DOTAP was equal to the molar concentration of DOTAP in the corresponding PE-LNPs. Blank PE-LNPs and unlabeled DOTAP liposomes were prepared at the same time. The FRET efficiency E at the specified time point was calculated according to formula (3):

[0136] E(%)=(I D -I DM ) / (I D )×100 Formula (3);

[0137] Among them, I D is the donor fluorescence intensity of NBD-PE labeled PE-LNPs at 530 nm after mixing with blank sample;

[0138] I DM is the donor fluorescence intensity of PE-LNPs after mixing with Rhod-PE labeled PE-LNPs.

[0139] Figure 6 Schematic diagram (A) and verification diagram (B-C) of the internal structure of the PE-LNP 11'-65' core without saRNA prepared by the present invention. The reference DOTAP-358 liposome, wherein the number (i.e., 358) indicates that its molar concentration is the same as the molar concentration of DOTAP present in PE-LNP 11'-65', both of which are 358mM. After incubating DOTAP-358 liposomes (NBD) and DOTAP-358 liposomes (Rhod) under the same conditions, it was observed that the FRET efficiency immediately increased to 17.1%, and then gradually increased to 22.0% after 1h, as shown in FIG. Figure 6As shown in B to C. This is because the lipid mixing between DOTAP liposomes leads to a decrease in the distance between the donor NBD and the acceptor Rhod, thus producing a more obvious FRET effect. However, no obvious FRET efficiency was observed after PE-LNP11'-65'(NBD) and PE-LNP 11'-65'(Rhod) were mixed for 1 hour, and it only increased slightly to 3.4% after extending the incubation to 2 hours. The negligible FRET efficiency indicates that the possibility of lipid mixing is very low, so the lipids are in the inner core of PE-LNP, such as Figure 6 As shown in Figure A.

[0140] Test Example 5

[0141] In vitro transfection efficiency

[0142] HEK293 cells were cultured at 5 × 10 4 The cells were seeded at a density of 100 μg / well in a 96-well plate and cultured in DMEM medium supplemented with 10% (v / v) fetal bovine serum and 1% (v / v) penicillin / streptomycin for 48 h until the cell density reached 60-80% before transfection. The medium was removed, 100 μL of fresh complete (or FBS-free) DMEM medium was added, and 10 μL of polymer-coated lipid nanoparticles loaded with saRNA prepared in Examples 16-23 were added (to make the concentration of each well 1 μg mL -1 saRNA). After 4 h of incubation, the transfection medium was replaced with fresh complete DMEM medium. After 24 h of incubation, 50 μL of medium was discarded from each well and 50 μL of fLuc substrate was added. The transfection efficiency was detected by Microplate Reader (Promega).

[0143] fLuc saRNA-attached PE-LNPs were prepared as follows for comparison. 650 μg PEG 5k -PCL 10kand 400 μg DOTAP were co-dissolved in 0.5 mL THF. The obtained organic solution was quickly added to 1 mL RNase-free water and stirred at room temperature for 1 to 2 min; then THF was removed by rotary evaporation to obtain blank PE-LNPs; then 10 μg fLuc saRNA was added to the blank PE-LNP solution. After 30 s of vortexing, fLuc saRNA-attached PE-LNPs were obtained. The transfection efficiency of fLuc saRNA-attached PE-LNPs was determined in the absence or presence of fetal bovine serum. PEI / fLuc saRNA complexes and fLuc saRNA-loaded DOTAP lipid nanostructures were prepared as controls. 100 μL RNase-free PBS (10×) buffer (or RNase-free water) was added to 900 μL fLuc saRNA-loaded PE-LNPs or fLuc saRNA-attached PE-LNPs solution and stored at 4°C. These freshly prepared or stored at 4°C for 5 days samples were then used to transfect HEK293 cells, and the transfection efficiency was determined as described above.

[0144] Figure 7 This is a comparison chart of the effects of polymer molecular weight, N / P molar ratio and polymer / nucleic acid mass ratio on transfection efficiency in the nucleic acid-loaded PE-LNP provided by the present invention, Figure 7 It can be seen that the effects of PEG-PCL molecular weight, N / P molar ratio and polymer / saRNA (w / w) weight ratio on the transfection efficiency of various PE-LNPs were evaluated in HEK293 cells. Figure 7 A and B show the transfection efficiency of PE-LNPs with a fixed polymer / saRNA (w / w) weight ratio of 65 but different N / P molar ratios. 2k -PCL 5k For PE-LNPs composed of PEG, the transfection efficiency increased by nearly four orders of magnitude when the N / P molar ratio increased from 5 to 16, and then decreased with further increases in the N / P molar ratio. 5k -PCL 10k The PE-LNPs composed of these two compounds showed a similar trend in transfection efficiency, but had a higher transfection efficiency at a lower N / P molar ratio of 5 and a higher peak transfection efficiency at an N / P molar ratio of 18. Figure 7 Panels C and D show the transfection efficiency of PE-LNPs with a fixed N / P molar ratio but different polymer / saRNA weight ratios. Figure 7 C indicates that for PEG 2k -PCL 5kFor PE-LNPs composed of 50% PEGylated saRNA, when the polymer / saRNA (w / w) weight ratio increased from 40 to 65, the transfection efficiency increased by two orders of magnitude; as the polymer / saRNA (w / w) weight ratio further increased to 90, the change in transfection efficiency became insignificant. Figure 7 D in the figure indicates that PEG 5k -PCL 10k For PE-LNPs composed of PEG and saRNA, the transfection efficiency was at a similar level within the tested polymer / saRNA (w / w) weight ratio range (40-90). This may be due to the fact that PEG with a higher molecular weight 5k -PCL 10k The resulting thicker polymer shell can provide better saRNA protection, which is achieved by not having FBS ( Figure 7 D) and in the presence of FBS ( Figure 7 In the case of PE-LNP (Fig. 2k -PCL 5k PE-LNPs composed of Figure 7 E). High serum compatibility is due to the greater stability of PE-LNP with a thicker polymer shell, which is beneficial for in vivo transfection, because many other cationic nucleic acid delivery systems with high in vitro transfection efficiency show lower in vivo transfection efficiency due to serum adsorption. Therefore, in the following work, we chose PEG 5k -PCL 10k Composition of PE-LNP.

[0145] Figure 8 The figure shows the in vitro transfection efficiency of PE-LNP with saRNA encapsulated inside and PE-LNP with saRNA adsorbed on the surface, as well as the transfection efficiency after storage under different conditions for a period of time. RNA molecules are very unstable and easily hydrolyzed / degraded. Two different RNA loading methods were used to compare the stability of RNA loaded in the core and attached to the surface of PE-LNP. Figure 8 As shown in Figure A, PE-LNP 18-80 loaded with saRNA and PE-LNP 18-80 with saRNA adsorbed on the surface showed comparable transfection efficiency in the absence of FBS, which was one order of magnitude higher than that of PEI / saRNA complexes and four to five orders of magnitude higher than that of saRNA-loaded DOTAP lipid nanostructures. Figure 8It can be seen from Figure B that PE-LNP 18-80 loaded with saRNA is compatible with FBS, and the presence of FBS causes the transfection efficiency of PE-LNP 18-80 with saRNA adsorbed on the surface to be reduced by one order of magnitude. In contrast, after incubation with FBS, the transfection efficiency of the PEI / saRNA complex was reduced by three orders of magnitude. This means that in the presence of FBS, PE-LNP 18-80 loaded with saRNA exhibits a transfection efficiency four orders of magnitude higher than that of the PEI / saRNA complex.

[0146] The stability of RNA encapsulated in the PE-LNP core or adsorbed on the surface after storage in RNase-free water or PBS at 4 °C was further evaluated. Figure 8 Middle C and Figure 8 As shown in D. After 5 days of storage, the transfection efficiency of PE-LNP18-80 encapsulated with saRNA did not decrease, while the transfection signal of PE-LNP18-80 adsorbed with saRNA on the surface was still relatively high (>10 6 ), but it was half an order of magnitude lower than that of freshly prepared samples. These results indicate that the saRNA-loaded PE-LNP system shows good serum stability and high encapsulation efficiency for RNA, especially for RNA molecules that are easily hydrolyzed / degraded, which can provide optimal protection. This is because the hydrophilic PEG corona of PE-LNPs can reduce protein absorption, while the hydrophobic PCL layer can protect RNA from the harsh external environment.

[0147] Test Example 6

[0148] PE-LNP-mediated mRNA transfection efficiency in the suspension cell line Jurkat

[0149] After loading messenger RNA (mRNA) encoding green fluorescent protein (GFP) with various PE-LNPs, Jurkat cells were transfected. PE-LNPs loaded with GFP mRNA were prepared according to the method of Example 20. Jurkat cells were diluted to 2×10 6 mL -1 Density, 1mL of cell suspension was inoculated into each well of a 12-well plate using serum-free RPMI-1640 medium. Then, PE-LNPs loaded with GFP mRNA were added dropwise at 2μg mRNA per well and gently blown with a pipette tip to mix evenly. After incubation at 37°C for 4h, the cells were washed twice with PBS, resuspended with 1ml of complete RPMI-1640 medium, and incubated at 37°C overnight. Cell viability was tested using the Vi-CELL XR cell viability analyzer. After rinsing with PBS twice, the cells were incubated with a LIVE / DEAD TMThe cells were stained with PBS and incubated for 30 min, then washed with PBS and observed under a fluorescence microscope (EVOS Floid Imaging System, ThermoFisher). The expression of GFP in living Jurkat cells was quantitatively analyzed by flow cytometry (Canto, BD, USA).

[0150] Fig. 9 A in the middle is a fluorescence microscopy comparison of Jurkat cells transfected with mRNA encoding green fluorescent protein (GFP) by different PE-LNPs; Fig. 9 Middle B is a bar graph showing the percentage of Jurkat cells expressing GFP in cells transfected with different PE-LNPs; Fig. 9 Middle C is a comparative bar graph of the mean fluorescence intensity after transfection; Fig. 9 D is a bar graph comparing cell survival rates after transfection. Fig. 9 Panel A shows that the expression of GFP mRNA was negligible in Jurkat cells treated with PE-LNP 5-11. Fig. 9 Middle B shows that when the polymer / mRNA (w / w) was fixed at 65, the percentage of Jurkat cells expressing GFP increased significantly to more than 60% as the N / P molar ratio increased from 5 to 11, and no significant enhancement was observed after further increasing the N / P molar ratio to 18. Fig. 9 Center C shows that the mean fluorescence intensity (MFI) exhibits a similar dependence on the N / P molar ratio. Fig. 9 D depicts that PE-LNP is well tolerated by Jurkat cells, and the results show that after 4 hours of treatment with PE-LNP 5-65 and PE-LNP 11-65, the cell viability is still close to 100%. Although some cytotoxicity was observed as the N / P molar ratio increased to 18, PE-LNP18-65 still showed a relatively high cell viability of 68.9±1.2%. In summary, PE-LNPs can also successfully transfect mRNA into suspension cell lines.

[0151] Test Example 7

[0152] Study on the mechanism of PE-LNP endocytosis and endosomal escape

[0153] 500 μg FITC, 800 μg PEG 5k -PCL 10k400 μg DOTAP was dissolved in 0.5 mL THF, and 10 μg saRNA was dissolved in 1 mL RNase-free water. The organic solution and the aqueous solution were quickly mixed and stirred for 1 to 2 minutes at room temperature. THF was removed by rotary evaporation, and free FITC was removed by centrifugation at 3000 r / min for 15 minutes in an ultrafiltration centrifuge tube (MWCO = 3000) to obtain PE-LNPs co-encapsulated with saRNA and FITC.

[0154] Fluorescence confocal microscopy was used to study the mechanism of cell internalization of PE-LNP. 2 mL of HEK293 cells (2 × 10 cells per culture dish) were taken. 5 Cells) were inoculated in 35 mm glass-bottomed culture dishes and cultured for 24 h. After pre-incubation at 4 °C for 1 h, saRNA- and FITC-co-encapsulated PE-LNPs were added (final saRNA concentration was 2 μg per dish), and the cells were incubated at 4 °C for another 4 h. HEK293 cells were treated with saRNA- and FITC-co-encapsulated PE-LNPs at 37 °C for 4 h as a control. After treatment at 4 °C or 37 °C, cells were washed with PBS, fixed with 4% paraformaldehyde solution for 10 min, and cell nuclei and lysosomes were stained with Hoechst 33342 (5 μg mL -1 The cells were then imaged using a Leica SP8 inverted confocal microscope, and the fluorescence colocalization of FITC and LysoTracker-Red was analyzed using Image J.

[0155] To further investigate the cellular uptake and intracellular trafficking mechanism of saRNA- and FITC-co-encapsulated PE-LNPs, HEK293 cells were cultured at 5 × 10 5 The cells were seeded at a density of 100 μg / well in a 6-well plate for 24 hours. First, the cells were incubated with the following inhibitors for 1 hour: chlorpromazine hydrochloride (10 μg mL -1 ), methyl-β-cyclodextrin (MβCD, 5 mM), filipin (5 μg mL -1 )、amiloride(1mM)、genistein(40μg mL -1 ) and nystatin (40 μg mL -1 ). Then, saRNA- and FITC co-encapsulated PE-LNPs (containing 2 μg saRNA) were added to each well and incubated with the inhibitor for 1 hour. Finally, the cells were washed three times with pre-cooled PBS solution and analyzed by flow cytometry (Fortessa I).

[0156] Take 2 mL of HEK293 cells (2 × 10 cells per cell) 5cells) were inoculated in 35 mm glass-bottomed culture dishes and cultured for 24 h. After pre-incubation with MβCD (5 mM) for 1 h, saRNA- and FITC-encapsulated PE-LNPs (containing 2 μg saRNA) were added to the culture dish and incubated with MβCD inhibitor for 4 h. The cells were then washed with PBS and fixed with 4% paraformaldehyde solution for 10 min. Hoechst 33342 (5 μg mL -1 ) and LysoTracker-Red (50 nM) were co-incubated with the cells for 5 minutes. Finally, the cells were observed using a Leica SP8 inverted confocal microscope.

[0157] Fig.10 Middle A is a confocal microscopy image showing the intracellular distribution of FITC-loaded PE-LNP 18-80 in HEK293 cells at 4 or 37°C for 4 h; Fig.10 B is Fig.10 The fluorescence intensity of FITC and Lysotracker corresponding to the cross section indicated by the horizontal line in A; Fig.10 Middle C is a confocal microscopy image showing the intracellular distribution of FITC-loaded PE-LNP 18-80 in HEK293 cells in the presence of the endocytosis inhibitor MβCD; Fig.10 D in the middle is the endocytosis of PE-LNP 18-80 by HEK293 cells in the presence of various endocytosis inhibitors detected by flow cytometry. Fig.10 As shown in Figure A, the intracellular green fluorescence intensity of FITC decreased significantly after incubation at 4°C for 4 h, indicating that the cellular uptake of PE-LNP is via an energy-dependent endocytosis pathway. Fig.10 Analysis in middle A shows that the fluorescence co-localization signal between saRNA and FITC co-loaded PE-LNP (green) and endosomes / lysosomes (red) is negligible. Fig.10 Figure B shows that PE-LNP successfully escaped from endosomal tissues. In addition, various endocytosis inhibitors were used to further study the specific endocytosis mechanism of PE-LNP. Fig.10 C and D show that the intracellular green fluorescence intensity was significantly reduced after treatment with the inhibitor MβCD, indicating that lipid raft-mediated endocytosis is the major cellular uptake pathway of PE-LNPs.

[0158] Test Case 8

[0159] Biosafety Evaluation of PE-LNP

[0160] The biocompatibility of saRNA-loaded PE-LNPs was studied by hemolysis. Defibrinated sheep red blood cells (RBC) were centrifuged at 1500×g for 10 minutes at 4°C and washed three times with PBS. The cell microspheres were resuspended in a 5% (v / v) red blood cell suspension with PBS. 100 μL of different PE-LNPs containing 1 μg of saRNA were added to 0.9 mL of RBC suspension and placed in a centrifuge tube. The red blood cell suspension was treated with deionized water as a positive control. After incubation at 37°C for 1 hour, the RBC suspension was centrifuged, and 100 μL of the supernatant was transferred to a 96-well plate and the plate was analyzed using a spectrofluorimeter ( The absorbance (A) was measured at 540 nm using a Discover Microplate Reader, Promega, USA. The relative hemolysis rate was calculated as follows: hemolysis rate (%) = ([Abs] sample - [Abs] buffer) / ([bs] DI water - [Abs] buffer) × 100.

[0161] The alamarBlue method was used to detect the cytotoxicity of saRNA-loaded PE-LNPs to HEK293 cells. HEK293 cells were cultured at 5×10 4 The cells were seeded at a density of 1 μg mL -1 Cells were treated with various PE-LNPs of saRNA for 4 h, and then 10 μL of alamarBlue HS reagent (5 mg mL -1 After incubation for another 4 h, the fluorescence spectrophotometer ( The absorbance of each well was measured at 570 nm using Discover Microplate Reader (Promega, USA) and the cytotoxicity was calculated.

[0162] Fig.11 A in the middle shows the hemolysis after incubation with various PE-LNPs at 37°C for 1 h; Fig.11 Figure B shows the viability of HEK293 cells treated with various PE-LNPs for 24 hours. Hemolysis and nonspecific cytotoxicity are toxicity issues associated with cationic carriers because they interact strongly with negatively charged cell membranes. Fig.11 As shown in Figure A, after 1 h of treatment, the hemolysis rates of various PE-LNPs were all lower than 10%, indicating that PE-LNPs have good biocompatibility. Fig.11 Figure B shows that HEK293 cells have good tolerance to saRNA-loaded PE-LNPs. -1At a fixed saRNA dose of , PE-LNP 5-65 and PE-LNP 11-65 showed very high cell viability of 92.3 ± 1.8% and 86.7 ± 1.4% after 24 hours of treatment, respectively. Although increased cytotoxicity was observed as the N / P molar ratio increased to 18, PE-LNP18-65 and PE-LNP18-80 still showed relatively high cell viability of 73.0 ± 4.9% and 73.6 ± 7.8%, respectively. These results indicate that PE-LNPs have low cytotoxicity and good biocompatibility.

[0163] Test Example 9

[0164] In vivo transfection effect and immune evaluation of PE-LNP in animals

[0165] Female BALB / c mice, 6 to 8 weeks old, were divided into 5 groups and housed in a fully acclimated room with free access to food and water. Animals were allowed at least 7 days of acclimatization before the start of the experiment. PE-LNPs 5-65, PE-LNPs 11-65, PE-LNPs 18-65, and PE-LNPs 18-80 containing 5 μg of fLuc saRNA were injected intramuscularly into the quadriceps of both hind legs of mice. saRNA-attached PE-LNP 18-80 was prepared as a control according to the method of Example 20. DOTAP (N / P=5) was used as a negative control group. After 7 days, mice were intraperitoneally injected with 100 μL XenoLight RediJect D-Luciferin substrate. After 10 minutes, the mice were anesthetized with isoflurane and the fluorescence was observed using the small animal imaging In Vivo Imaging System FX Pro (Kodak Co., Rochester, NY, USA). The fluorescence intensity of the same detection area at each injection site was quantified and expressed as RLU.

[0166] Female BALB / c mice, 6 to 8 weeks old, were divided into 5 groups. 50 μL (saRNA concentration of 20 μg / mL) of PE-LNP11-65, PE-LNP 18-65 and PE-LNP 18-80 loaded with saRNA (HA saRNA) encoding Cal / 09 virus H1 hemagglutinin were injected into the quadriceps muscle of the hind legs of mice, and a second booster immunization was performed 4 weeks later. The jetPEI / HA saRNA complex was used as the control group. Blood was collected through the tail vein 4 and 6 weeks after the start of the study. Serum was collected by centrifugation at 10000× RPM for 5 min and stored at -80°C. HA antibody titer was quantitatively evaluated by immunoglobulin ELISA protocol. 0.5 μg / mL HA-coated ELISA plates were blocked with 1% (w / v) BSA / 0.05% (v / v) Tween-20 in PBS. After washing, the diluted serum samples were added to the plate, incubated for 2 hours, then washed and anti-mouse IgG-HRP (Southern Biotech, UK) diluted 1:4000 was used. Standards were prepared by coating ELISA plate wells with anti-mouse Kappa (1:1000) and Lambda (1:1000) light chains (Serotec, UK), blocked with PBS / 1% (w / v) BSA / 0.05% (v / v) Tween-20, washed and added with purified IgG (Southern Biotech, UK) at a starting concentration of 1000 ng / mL, and titrated with a 5-fold dilution series. Samples and standards were developed using TMB (3,3'; 5,5'-tetramethylbenzidine) and the reaction was stopped after 5 minutes with stop solution (Insight Biotechnologies, UK). The absorbance was read with SoftMax Pro GxPv5 software on a spectrophotometer (VersaMax, Molecular Devices).

[0167] 0.5 μg / mL HA coated ELISA plates were blocked with 1% (w / v) BSA / 0.05% (v / v) Tween-20 in PBS. After washing, the diluted serum samples were added to the plates, incubated for 2 h, washed, and then treated with anti-mouse IgG-HRP (Southern Biotech, UK) diluted 1:4000. Standards were prepared by coating ELISA plate wells with anti-mouse Kappa (1:1000) and Lambda (1:1000) light chains (Serotec, UK), blocking with PBS / 1% (w / v) BSA / 0.05% (v / v) Tween-20, washing, and adding purified IgG (Southern Biotech, UK) starting at 1000 ng / mL and titrating with a 5-fold dilution series. TMB (3,3'; 5,5'-tetramethylbenzidine) was used to prepare samples and standards, and the reaction was stopped after 5 minutes using stop solution (Insight Biotechnologies, UK). The absorbance was read on a spectrophotometer (VersaMax, Molecular Devices) using SoftMax Pro GxP v5 software.

[0168] Three weeks after the second immunization, 4.2×10 5 Mice were challenged with pfu influenza virus (Cal / 09). Mice were anesthetized with isoflurane, challenged via the nasal mucosa, and weighed daily to determine weight loss.

[0169] Fig.12 The figure is a comparison of the protein expression efficiency of different PE-LNP in mice, the antibody content in mice after immunization, and the weight change after virus stimulation after immunization. Fig.12 It can be seen that after 7 days, all PE-LNP groups showed protein expression. The protein expression signal of mice treated with saRNA / DOTAP lipid nanostructures was almost undetectable, which may be due to the limited encapsulation capacity and poor stability of saRNA / DOTAP lipid nanostructures ( Fig.12 A). Fig.12As shown in Figure B, the three formulations PE-LNP 11-65, PE-LNP 18-65, and PE-LNP 18-80 showed significantly higher luciferase expression compared to PE-LNP 5-65 (p<0.05). PE-LNP 18-80 M2 is a formulation in which saRNA is adsorbed on the surface of polymer-coated lipid nanoparticles. Although it shows similar in vitro transfection efficiency as PE-LNP 18-80 loaded with saRNA, in vivo luciferase expression in PE-LNP18-80 M2 is significantly lower than that in PE-LNP 18-80 (p<0.05), which further confirms that encapsulating saRNA inside PE-LNPs is more advantageous than adsorbing saRNA on the surface. Although the in vitro transfection efficiency of PE-LNP18-65 is one order of magnitude higher than that of PE-LNP11-65, the in vivo luciferase expression of the two groups presents similar signals. This may be because PE-LNP 11-65 has lower cytotoxicity.

[0170] In addition, the immunogenicity and protective capacity of PE-LNP loaded with saRNA encoding HA after IM injection were evaluated. Commercially available jetPEI was used as a positive control. Mice received primary and booster immunizations of formulations prepared with jetPEI, PE-LNP 11-65, PE-LNP 18-65 and PE-LNP 18-80. Booster immunizations were performed 4 weeks after the initial immunization. Fig.12 Middle C shows that mice were challenged IN with Cal / 09 influenza virus 2 weeks after booster immunization and weighed daily to monitor disease progression. All mice in the blank group lost >25% of their body weight after day 6 and had to be euthanized. Fig.12 Middle E shows that all mice in the jetPEI and PE-LNPs groups were completely protected. During the entire observation period, the mice in all PE-LNPs groups lost less than 10% of their body weight, especially the PE-LNP11-65 group, which had the least weight loss (about 8%), indicating less side effects and better protection. HAIgG antibody titer ( Fig.12 Middle D) directly reflects the result of immune protection. PE-LNP11-65, PE-LNP 18-65, and PE-LNP 18-80 all induced high antibody titers, but there was no significant difference (about 1×10 5 ng mL -1 ), which is comparable to jetPEI. Fig.12 The in vivo protein expression results shown in B are consistent. This indicates that all PE-LNPs groups reached the protein expression threshold required to stimulate immune responses. Therefore, PE-LNPs have greater flexibility in formulation while ensuring effectiveness, which is beneficial for the delivery of biomacromolecules including RNA vaccines and therapeutics.

[0171] Test Example 10

[0172] Stability study of PE-LNP liquid preparation

[0173] PE-LNP 11-65, PE-LNP 18-65, PE-LNP 18-65 and PE-LNP 18-80 (with saRNA concentration of 40 μg mL -1 ) were stored at 4°C for a period of time. Then, the samples were taken out at a specific time point and transfected with different batches of HEK293 cells at the same time according to the above method. The saRNA dose during the transfection process was 1 μg mL -1 The culture medium was FBS-free. Freshly prepared samples were selected as controls.

[0174] Fig.13 The figure is a comparative bar graph of the transfection efficiency of HEK293 cells after different PE-LNP liquid states were stored at 4°C for different periods of time. Fig.13 It can be seen that the transfection efficiency of liquid preparations with different compositions did not decrease significantly when stored at 4°C for 38 days, indicating that PE-LNP has its unique advantages in RNA preservation. For some samples, there will be some fluctuations in the transfection signal when tested at different time points, which is caused by the differences between different batches of samples.

[0175] Test Example 11

[0176] Optimization of PE-LNP freeze-dried formulation conditions

[0177] RNA molecules are very fragile and can easily degrade in exposed environments, so RNA vaccines and therapeutics need to be stored and transported in a very challenging cold chain. Pfizer / BioNTech's mRNA vaccine is the world's first approved COVID-19 vaccine, but faces the need to be stored at -70°C. Other RNA vaccines have similar thermal stability issues, such as Moderna's mRNA vaccine, which needs to be stored at -20°C. This makes it extremely challenging for RNA vaccines to achieve the required deployment speed and scale to ensure herd immunity. PE-LNP 11-65 showed efficient in vivo protein expression and excellent immunogenicity, so PE-LNP 11-65 was selected for further study of RNA stability and non-cold chain storage. The poor stability of saRNA delivery systems in aqueous media is a real obstacle limiting their clinical application. Since RNA can cause spontaneous catalytic hydrolysis, one strategy to improve the stability of RNA vaccines is to remove the aqueous solution. PE-LNPs 11-65 showed good in vivo protein expression and immunogenicity, so PE-LNPs 11-65 were selected for the following stability and non-cold chain storage studies. Lyophilizing PE-LNPs by adding stabilizing molecules such as trehalose to the outside and / or inside of PE-LNPs allows them to be stored stably without the need for a cold chain. However, the lyophilization process may severely reduce the colloidal stability of RNA delivery nanoformulations, leading to irreversible efficacy reduction. The colloidal stability of nanoparticles can be improved by simply mixing trehalose on the outside of the nanoparticles during the freeze-drying process, because the vitrification of trehalose can fix the nanoparticles in a rigid, amorphous glass sugar matrix and significantly reduce the aggregation or breakage of the nanoparticles. In addition, due to the unique structure of PE-LNPs containing internal hydrophilic domains, trehalose can also be co-loaded with RNA inside PE-LNPs and directly interact with RNA. The hydroxyl groups of trehalose can form hydrogen bonds with RNA molecules, thereby minimizing the interaction of RNA with water during the lyophilization process. Therefore, the thermal stability of RNA can be significantly improved.

[0178] Formulations containing trehalose only on the outside of saRNA-loaded polymer-coated lipid nanoparticles were prepared. -1 , 40 μg mL -1 , 60 μg mL -1 and 100 μg mL -1 )PE-LNP 11-65. The obtained nanoparticles were then mixed with trehalose such that the trehalose was on the outside of the nanoparticles and the concentration was fixed at 200 mg mL -1 The preparations were frozen in a -80 °C freezer, lyophilized for 48 h, and then immediately rehydrated with RNase-free water. 1 μg mL-1 DLS particle size distribution of rehydrated PE-LNPs and in vitro HEK293 cell transfection efficiency at saRNA doses to optimize the saRNA concentration during freeze-drying. PE-LNPs 11-65 with optimized saRNA concentration were then incubated with different concentrations of external trehalose (e.g., 150 mg mL -1 , 200mg mL -1 , 250mg mL -1 , 300mg mL -1 and 400 mg mL -1 ) were mixed and lyophilized, and immediately rehydrated with RNase-free water and further analyzed by DLS and in vitro transfection. The optimal concentration of loaded saRNA and mixed trehalose of lyophilized PE-LNP11-65 was finally determined.

[0179] Fig.15 A in the middle is a comparison of the transfection efficiency of lyophilized saRNA-loaded PE-LNP 11-65 (with different saRNA concentrations before lyophilization and only trehalose on the outside) after reconstitution, where the NC group represents the freshly prepared PE-LNP 11-65 (no trehalose) negative control, (*) and (***) indicate p<0.05 and p<0.001, respectively; Fig.15 B is PE-LNP 11-65 (40 μg mL -1 saRNA) mixed with different concentrations of trehalose and then freeze-dried and reconstituted HEK293 cells transfection efficiency, freshly prepared PE-LNP 11-65 (without trehalose) was used as a negative control. -1 ) of PE-LNP 11-65 and controlled its external trehalose concentration to 200 mg mL -1 , were lyophilized and then immediately rehydrated with RNase-free water. The transfection efficiency of the rehydrated PE-LNP 11-65 was evaluated. Fig.15 Panel A (where (*) and (***) indicate p<0.05 and p<0.001, respectively) shows the synergistic effect of external trehalose on HEK293 cell transfection, with all freeze-dried PE-LNP 11-65 preparations increasing transfection efficiency by 1 to 1.5 orders of magnitude compared to freshly prepared trehalose-free PE-LNP. Fig.15 Medium A, select 40 μg mL -1 As 200mg mL -1 Optimal saRNA concentration of lyophilized saRNA-loaded PE-LNP 11-65 in the presence of external trehalose.

[0180] In addition, the saRNA concentrations with a fixed concentration (40 μg mL -1 ) and transfection efficiency of PE-LNP11-65 after freeze-drying and immediate hydration with different external trehalose concentrations. Fig.15 Medium B, choose 250mg mL -1 As the optimal external trehalose concentration for freeze-drying loading 40 μg mL -1 PE-LNP 11-65 with saRNA inside. Fig.15 As shown in Figure B, the lyophilized preparation under this condition showed the highest transfection efficiency after immediate rehydration, which was one order of magnitude higher than the freshly prepared trehalose-free PE-LNP11-65 at the same dose.

[0181] Will contain 250mg mL -1 External trehalose loaded with saRNA (40 μg mL -1 ) PE-LNP 11-65 was lyophilized and then stored at 4°C for 28 days. Afterwards, the lyophilized PE-LNP was rehydrated with RNase-free water to a concentration of 1 μg mL- 1 The in vitro transfection efficiency of HEK293 cells was measured at different saRNA doses.

[0182] Fig.16 For PE-LNP 11-65 (40 μg mL -1 saRNA) external trehalose concentration was 250 mg mL -1 In the case of , lyophilized and stored at 4 ° C for 28 days, after reconstitution with RNase-free water, the transfection efficiency of HEK293 cells was evaluated, and freshly prepared PE-LNP 11-65 (without trehalose) was used as a negative control. Fig.16 It can be seen that the lyophilized PE-LNP 11-65 (saRNA concentration before lyophilization is 40 μg mL -1 , external trehalose 250mg mL -1 ) was stored at 4°C for 28 days and then reconstituted. Compared with freshly prepared PE-LNP 11-65 without trehalose, its transfection efficiency was not significantly reduced at the same saRNA dose. This indicates that the combined effect of external trehalose and the intrinsic protection provided by the core-shell PE-LNP nanostructure well maintains the stability of RNA during storage at 4°C.

[0183] The protective effect and stability of internally loaded trehalose on saRNA-loaded PE-LNP were further studied. First, part of the trehalose was dissolved in 40 μg mL -1The saRNA solution was added to obtain the assembled PE-LNP 11-65 according to the above method. Then, the remaining trehalose was mixed with the obtained saRNA and trehalose co-encapsulated PE-LNP11-65 to make the total trehalose (internal and external) concentration reach 250 mg mL -1 At a trehalose / saRNA (w / w) ratio of 6250 and a saRNA concentration of 40 μg mL -1 After lyophilization and immediate reconstitution with RNase-free water, the colloidal stability of saRNA and trehalose co-loaded PE-LNP 11-65 was tested by DLS and their stability at a saRNA dose of 1 μg mL -1 In vitro transfection efficiency of HEK293 cells.

[0184] The results showed that when the trehalose / saRNA (w / w) weight ratio was greater than 400, the size of the nanoparticles reconstituted with RNase-free water after freeze-drying was greater than 300 nm. The trehalose / saRNA weight ratio of 100 was the most favorable, and its rehydrated PE-LNP 11-65 had a particle size of 167.7 ± 3.6 nm and good monodispersity, with a PDI of 0.313 ± 0.017, which was not much different from the freshly prepared trehalose-free PE-LNP11-65 (size = 131.3 ± 0.5 nm and PDI = 0.265). This shows that the presence of internal and external trehalose well preserves the colloidal stability of PE-LNP 11-65 during freeze-drying and rehydration. In addition, the saRNA encapsulation efficiency of PE-LNP 11-65 co-loaded with saRNA and trehalose was as high as 85.2±4.8%, which was comparable to that of PE-LNP 11-65 without trehalose (93.6±3.2%).

[0185] Increasing the trehalose / saRNA (w / w) weight ratio to 50-100 (i.e., increasing the proportion of internal trehalose) for freeze-dried PE-LNP 11-65 has higher transfection efficiency. Fig.17 The total trehalose (inside and outside PE-LNP 11-65) concentration was 250 mg mL -1 Effect of trehalose / saRNA mass ratio on in vitro transfection efficiency of freeze-dried samples during PE-LNP preparation under the same conditions. Freshly prepared PE-LNP 11-65 (without trehalose) was used as negative control. (***) and (****) indicate p<0.001 and p<0.0001, respectively. Fig.17It can be seen that when the trehalose / saRNA (w / w) weight ratio is 100, its transfection efficiency is 1.5 orders of magnitude higher than that of the freshly prepared PE-LNP 11-65 formulation without trehalose. Further increase of the trehalose / saRNA (w / w) weight ratio to above 100 will reduce the transfection efficiency, although it is still one order of magnitude higher than that of freshly prepared PE-LNP 11-65. This shows that the coexistence of trehalose inside and outside PE-LNP can play a synergistic role and significantly improve the stability and efficacy of RNA. In summary, the optimized lyophilization conditions for saRNA and trehalose co-loaded PE-LNP 11-65 are: 40μg mL -1 saRNA and trehalose / saRNA weight ratio = 100 for co-encapsulation, then mixed with additional trehalose to bring the total trehalose concentration to 250 mg mL -1 ) for freeze-drying.

[0186] Test Example 12

[0187] Study on thermal stability of freeze-dried preparations

[0188] The optimized saRNA and trehalose co-encapsulated PE-LNP 11-65 formulations were lyophilized and then stored at 40°C. PE-LNP 11-65 loaded with saRNA mixed with external trehalose was lyophilized as a control. After storage for a period of time, the lyophilized PE-LNP11-65 formulation was rehydrated with RNase-free water and its in vitro transfection efficiency was measured.

[0189] After the samples of saRNA and trehalose co-encapsulated PE-LNP 11-65 and saRNA-encapsulated PE-LNP 11-65 mixed with external trehalose were stored at 40°C for 7 days, ultrafiltration centrifugation was used to remove the free (unencapsulated) external trehalose after lyophilization, and then their in vitro transfection efficiency was determined after hydration.

[0190] To evaluate the potential of PE-LNPs co-loaded with RNA and trehalose under non-cold chain storage, the optimized PE-LNPs 11-65 co-loaded with saRNA and trehalose were lyophilized and stored at 40 °C for 1, 3, 5, 7 or 14 days, respectively. Fig.18 The figure is a comparison of the transfection efficiency of freeze-dried PE-LNP 11-65 with trehalose only on the outside and trehalose both inside and outside after being reconstituted at 40°C for different time periods, where NC is the negative control group, (*), (**), (***) and (****) represent p<0.05, p<0.01, p<0.001 and p<0.0001, respectively. Fig.18It can be seen that the transfection efficiency of saRNA-loaded PE-LNP 11-65 (containing trehalose both inside and outside) and PE-LNP 11-65 containing trehalose only on the outside was about 1.5 orders of magnitude higher than that of freshly prepared PE-LNP 11-65 without trehalose, which further confirmed the synergistic effect of trehalose. Fig.19 The transfection efficiency of the lyophilized preparation containing trehalose both inside and outside of PE-LNP 11-65 stored at 40°C for 14 days after reconstitution, where NC is the negative control of freshly prepared PE-LNP without trehalose, and ns indicates no significant difference between the two groups. Fig.19 It can be seen that even after being stored at a high temperature of 40°C for 14 days, the transfection efficiency of PE-LNP11-65 co-loaded with saRNA and trehalose was not significantly reduced compared with freshly prepared PE-LNP 11-65 without trehalose, indicating that RNA has excellent thermal stability and efficacy at room temperature and even tropical conditions.

[0191] Then, the lyophilized samples (PE-LNP 11-65 co-encapsulated with saRNA and trehalose and PE-LNP 11-65 containing only trehalose on the outside) were stored at 40°C for 7 days and then rehydrated. The free external trehalose was removed by ultrafiltration centrifugation to detect the transfection efficiency. Fig. 20 The transfection efficiency of the freeze-dried preparation containing trehalose both on the outside and inside of PE-LNP after being stored at 40℃ for different time periods and then reconstituted and then the external trehalose was removed. Among them, PE-LNP 11-65 containing only external trehalose and freshly prepared NC without trehalose were used as the control group; (*), (**), (***) and (****) indicate p<0.05, p<0.01, p<0.001 and p<0.0001, respectively. Fig. 20 It can be seen that after the removal of external trehalose, the transfection efficiency of PE-LNP 11-65 containing only trehalose on the outside was significantly reduced compared with the sample without ultrafiltration centrifugation, especially on the 7th day of storage at 40°C. The transfection efficiency of saRNA and trehalose co-encapsulated PE-LNP 11-65 after rehydration after storage at 40°C for 7 days was comparable to that of freshly prepared trehalose-free PE-LNP11-65. These results further confirm the key role of internal trehalose in enhancing the thermal stability and efficacy of co-encapsulated RNA in PE-LNP.

[0192] Test Example 13

[0193] Study on the synergistic effect of trehalose on PE-LNP transfection

[0194] Trehalose and calcein (50 μg mL -1) and saRNA were dissolved in RNase-free deionized water, wherein trehalose / saRNA (w / w=100), and saRNA-, trehalose-, and calcein-co-loaded PE-LNP11-65 were prepared according to the method of Example 20, and additional trehalose was mixed therein to add to a total trehalose (internal and external) of 250 mg mL -1 PE-LNP 11-65 (without trehalose) co-loaded with saRNA and calcein was prepared as a control. The cell uptake and intracellular transport of the two preparations were studied by laser scanning confocal microscopy. 2 mL of HEK293 cells (2 × 10 per culture dish) were cultured in 4% paraformaldehyde and 1% paraformaldehyde. 5 Cells) were inoculated into 35mm glass bottom culture dishes and cultured for 24 hours. The two preparations were added to the culture dishes (2μg saRNA per dish). After 2 hours of treatment, the cells were washed and supplemented with complete medium and cultured for another 4 hours. The cells were imaged using a Leica SP8 inverted confocal microscope, and the mean fluorescence intensity of calcein in the confocal microscope images was analyzed by ImageJ.

[0195] The membrane-impermeable dye calcein was co-loaded into both PE-LNP 11-65 samples as an indicator of cellular uptake and intracellular uptake. Fig.21 Middle A is a confocal microscopy image of HEK293 cells treated with freshly prepared saRNA and calcein co-encapsulated PE-LNP 11-65 and saRNA, trehalose, and calcein co-encapsulated PE-LNP 11-65 4 hours after treatment; Fig. 22 B is a quantitative analysis of the mean fluorescence intensity of calcein in confocal microscopy images analyzed by ImageJ, **** indicates p < 0.0001. Fig.21 As shown in the confocal microscopy images ( Fig.21 Middle A), HEK293 cells treated with freshly prepared saRNA, trehalose and calcein co-loaded PE-LNP 11-65 showed significantly stronger green diffuse fluorescence compared to cells treated with freshly prepared saRNA and calcein co-loaded LNP 11-65. The mean fluorescence intensity (MFI) was analyzed by ImageJ. Fig.21 Figure B shows that the MFI of cells treated with saRNA, trehalose and calcein co-loaded PE-LNP 11-65 was significantly higher than that of cells treated with saRNA and calcein co-loaded PE-LNP 11-65. This confirms that the presence of trehalose can enhance cellular uptake and subsequent endosomal escape.

[0196] PE-LNP 11-65 co-loaded with trehalose and mRNA expressing GFP (trehalose / mRNA weight ratio = 100) was used for co-encapsulation and then mixed with additional trehalose to add to 10 mg mL -1 Total trehalose) was prepared as described in the previous section. PE-LNP 11-65 without trehalose was prepared as a control. HEK293 cells were cultured at 5×10 5 The cells were inoculated into 6-well plates and cultured for 48 hours. The in vitro transfection was quantitatively analyzed by flow cytometry (Canto, BD, USA).

[0197] Fig. 22 A in the middle is the ratio of PE-LNP 11-65 co-encapsulated with mRNA encoding GFP and trehalose and PE-LNP 11-65 loaded with mRNA alone expressing GFP green fluorescence after being treated with HEK293 cells; Fig. 22 B in the figure is the mean fluorescence intensity (MFI) of GFP expression in cells; * and ** indicate p<0.05 and p<0.01, respectively. Fig. 22 As shown in Figure 2A, the percentage of HEK293 cells expressing GFP increased from 51.9 ± 4.9% to 74.2 ± 2.2% after the treatment of mRNA and trehalose co-loaded PE-LNP 11-65 compared with freshly prepared trehalose-free PE-LNP 11-65, which increased by 1.7-fold compared with the MFI of freshly prepared trehalose-free PE-LNP11-65 ( Fig. 22 This further confirms the synergistic effect of PE-LNP-based trehalose on the intracellular delivery of various nucleic acids.

[0198] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A polymer-coated lipid nanoparticle, comprising a polymer vesicle and a lipid and a load encapsulated in the polymer vesicle; the polymer constituting the polymer vesicle is an amphiphilic block copolymer; the amphiphilic block copolymer contains a hydrophilic polymer block and a hydrophobic polymer block; the amphiphilic block copolymer is PEG 5K -PCL 10K or PEG 2K -PCL 5K ; The mass ratio and molar ratio of the amphiphilic block copolymer to the lipid are as follows: The lipid comprises a cationic lipid, and the cationic lipid is (2,3-dioleoyl-propyl)-trimethylammonium chloride; the particle size of the polymer-wrapped lipid nanoparticles is 50-200 nm.

2. The polymer-encapsulated lipid nanoparticle according to claim 1, characterized in that: The polymer-wrapped lipid nanoparticle further comprises a stabilizer, which is wrapped inside the polymer-wrapped lipid nanoparticle and / or located outside the polymer-wrapped lipid nanoparticle.

3. The polymer-encapsulated lipid nanoparticles according to claim 2, characterized in that: The stabilizer includes one or more of carbohydrates, polyols and surfactants.

4. The polymer-encapsulated lipid nanoparticle according to claim 2, characterized in that: The stabilizer also includes one or both of a pharmaceutically acceptable complex and a pharmaceutically acceptable salt.

5. The polymer-encapsulated lipid nanoparticle according to any one of claims 1 to 4, characterized in that: The polymer-encapsulated lipid nanoparticles further include a targeting ligand.

6. A method for preparing polymer-encapsulated lipid nanoparticles according to any one of claims 1 to 5, comprising the following steps: The amphiphilic block copolymer and lipid are dissolved in an organic solvent to obtain an organic phase; the mass percentage of the hydrophilic polymer block in the amphiphilic block copolymer is 20-50%; the lipid includes a cationic lipid, and the cationic lipid is (2,3-dioleoyl-propyl)-trimethylammonium chloride; The organic phase is mixed with water for self-assembly coating, and the organic solvent is removed to obtain the polymer-coated lipid nanoparticles.

7. A pharmaceutical preparation comprising polymer-coated lipid nanoparticles; the polymer-coated lipid nanoparticles are the polymer-coated lipid nanoparticles according to any one of claims 1 to 5 or the polymer-coated lipid nanoparticles prepared by the preparation method according to claim 6; the load in the lipid nanoparticles comprises nucleic acids.

8. The pharmaceutical preparation according to claim 7, characterized in that: The mass ratio of the amphiphilic block copolymer to the load in the polymer-encapsulated lipid nanoparticles is 5-1000:1.

Citation Information

Patent Citations

  • Tubular and vesicular architectures formed from polymer-lipid blends and method for forming the same

    CN107735170A

  • Submicron particles

    CN118234485A

  • Controlled release polymersomes

    US20050003016A1

  • Amphiphile-Polymer Particles

    US20170304213A1